Charged cyclodextrin polymer materials and methods for making and using same - Patents.com

Crosslinked cyclodextrin polymers improve PFAS removal from water by enhancing adsorption capacity and selectivity, overcoming the inefficiencies of traditional adsorbents with rapid uptake and easy regeneration.

JP7607347B2Active Publication Date: 2024-12-27CYCLOPURE INC
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
JP2022164796
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2019-02-14
Filing Date
2022-10-13
Publication Date
2024-12-27
Estimated Expiration
2040-02-13

AI Technical Summary

Technical Problem

Existing adsorption methods, particularly activated carbon, struggle to effectively remove anionic micropollutants like PFAS from water due to low affinity, slow uptake rates, and high energy consumption for regeneration, lacking optimal selectivity and efficiency.

Method used

Development of porous polymeric materials composed of crosslinked cyclodextrins with specific crosslinking agents, such as aryl or heteroaryl moieties, to enhance adsorption capacity and selectivity for anionic micropollutants, allowing for rapid extraction and easy regeneration.

Benefits of technology

The crosslinked cyclodextrin polymers demonstrate enhanced adsorption capacity and selectivity for PFAS, achieving rapid uptake and efficient regeneration, addressing the limitations of traditional adsorbents.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007607347000068
    Figure 0007607347000068
  • Figure 0007607347000069
    Figure 0007607347000069
  • Figure 0007607347000070
    Figure 0007607347000070
Patent Text Reader

Abstract

Charged cyclodextrin polymer materials and methods for making and using same are provided. The present disclosure relates to charged polymeric materials and methods of their use for purifying fluid samples from trace contaminants, such as anionic trace contaminants. The present disclosure provides charged cyclodextrin polymeric materials and methods for making and using the same. In some embodiments, the present disclosure provides articles of manufacture comprising the porous polymeric materials or supported porous polymeric materials of the present disclosure.
Need to check novelty before this filing date? Find Prior Art

Description

[Background technology]

[0001] Organic micropollutants (MPs) are present in concentrations ranging from ngL -1 ~μgL -1 present in water resources at concentrations of 1,2 Human health 3~7 and the environment 8~10 Due to concerns about the negative impact of MP on the environment, efforts are underway to develop technologies that can more effectively remove MP. 11~16 MPs vary widely in their physicochemical properties, including surface charge, size, and chemical functionality. Charged MPs can be cationic, anionic, or zwitterionic, and are typically difficult to remove using traditional adsorption methods, such as activated carbon, in the presence of complex matrix components, such as natural organic matter (NOM). Among the anionic MPs, PFAS are of particular environmental concern due to their resistance to biodegradation and correlation with adverse health effects. PFAS are used in the formulation of thousands of consumer products. 1 , which is included in water-based foam formulations used to suppress aviation fires in training situations. 18,19 As a result, PFAS have contaminated surface and groundwater near thousands of airports and military facilities. 20 In 2016, Hu and colleagues reported that at least 6 million Americans are at or near the 2016 U.S. Environmental Protection Agency's health advisory limit of 70 ng / L for perfluorooctanoic acid (PFOA) and perfluorooctanesulfonic acid (PFOS). -1 indicated that they were provided with drinking water contaminated with PFAS or 21 PFAS are known to cause cancer 3 , liver damage 4 , thyroid disease 5 , and other health problems 6 .

[0002] Contaminated water systems are typically remediated with granular activated carbon (GAC), but this is an expensive, temporary solution due to its lack of affinity for PFAS, especially the short-chain derivatives. 23,24 In a recent report 14,15It was found that non-covalent interactions and electrostatic charges of functional groups influence the affinity of PFAS for the adsorbent. For example, the combination of fluorophilic interactions of the crosslinker and low concentrations of anionic charged functional groups in decafluorobiphenyl-bridged CDPs resulted in high removal rates of PFOA and PFOS from water. In contrast, CDPs crosslinked by epichlorohydrin showed low removal rates of PFAS. 25 .

[0003] Adsorption processes can be used to remove specific pollutants or pollutant classes from fluids such as air and water. Activated carbons (ACs) are the most widespread adsorbents used for the removal of organic pollutants, and their effectiveness is primarily derived from their high surface area, nanostructured pores, and hydrophobicity. However, not one type of AC can provide good removal of all pollutants, especially anionic MPs. Due to their poorly defined structure and varying binding sites, optimal adsorption selectivity requires empirical screening on new installations, thus precluding rational design and improvement. In addition, regeneration of spent ACs is energy intensive (heating to 500-900 °C or other energy-intensive procedures) and full performance is not restored. ACs also have a slow rate of pollutant uptake, reaching their uptake equilibrium in hours to days, so excess adsorbent is required for more rapid pollutant removal. Finally, ACs may not perform well for many emerging pollutants, especially those that are relatively hydrophilic.

[0004] An alternative adsorbent material can be produced from polymeric cyclodextrin materials generated from insoluble polymers of β-cyclodextrin (β-CD). This material is a toroidal macrocyclic compound composed of seven glucose units with an internal cavity capable of binding organic compounds. β-CD is an inexpensive and sustainably produced monomer derived from corn starch and is widely used in the formulation and stabilization of pharmaceuticals, flavors, and fragrances, as well as stationary phases in chiral chromatography. The insoluble β-CD polymers are formed by crosslinking epichlorohydrin with other reactive compounds, and contain well-defined binding sites and It is characterized by a high association constant. Insoluble β-CD polymers crosslinked with epichlorohydrin have been investigated as a replacement for AC for water purification, but their sorbent performance is inferior to that of AC due to their low surface area.

[0005] Thus, there is a need for new sorbents that overcome the shortcomings of AC and the like and provide more effective sorption and / or sequestration properties for MPs, such as anionic MPs. There is a need for sorbents that provide rapid anionic MP extraction, high total uptake, and easy regeneration and reuse procedures. The present invention meets these needs. Summary of the Invention [Means for solving the problem]

[0006] In some embodiments, the present disclosure provides a compound of formula (I): [ka] a porous polymeric material comprising a plurality of cyclodextrins crosslinked with a plurality of bridges having During the ceremony, A is an aryl or heteroaryl moiety; Each R 1 is H, C1-C6 alkyl, C1-C3 haloalkyl, aryl, heteroaryl, -CF3, -SO3H, -CN, -NO2, -NH2, -NCO, -C(O)2R 3 , -C(O)N(R 3 -halogen; Each R 2 are independently H, -OH, -O-metal cation, alkyl, aryl, heteroaryl, -SH, -S-metal cation, -S-alkyl, -C(O)H, or -C(O)NH; Each R 3 are independently -H, -C1-C6 alkyl, -C1-C3 haloalkyl, aryl, -C(O)N(R a )(R b ), -C(O)Rc , -CO2R c , -SO2N(R a )(R b ), or -SOR c And each R a and R b are independently H or C1-C6 alkyl; Each W is independently a bond, an alkylene group, an arylene group, a heteroarylene group, -O-arylene-, -(CH) a -Arylene-, -SO2-arylene-, -NH-arylene-, -S-arylene-, -O-heteroarylene-, -(CH2) a -Heteroarylene-, -SO2-heteroarylene-, -NH-heteroarylene-, -S-heteroarylene-, -(-O-(CH2) a -) x -, -(-NH-(CH2) a -) x -, -(-S-(CH2) a -) x -, [ka] wherein a is 0 to 100, x is 1 to 100, and each arylene or heteroarylene moiety may be substituted or unsubstituted; each Z is a cationic or anionic moiety; Each L is independently -O-, -S-, -N-, a C1-C6 substituted or unsubstituted alkylene, a C1-C3 haloalkylene, [ka] is a linking moiety selected from the group consisting of A' is a covalent bond to A, Z' is a covalent bond to Z; *teeth, [ka] is a covalent bond to [ka] is the point of attachment to multiple cyclodextrin carbon atoms, x is 0 to 8; y1 is 1 to 4; y2 is 1 to 4; y3 is 0 to 4.

[0007] In some embodiments, the crosslinking of the porous polymeric material is represented by formula (II): [ka] having During the ceremony, y2 is 1 or 2; x is 1 or 2.

[0008] In some embodiments, the porous polymeric material of the present disclosure has formula (III): [ka] and a plurality of linkers of Wherein, one R 4 is -H and one R 4 is -Me.

[0009] In some embodiments, the present disclosure provides a supported porous polymeric material comprising a porous particle immobilized on a solid substrate, said porous particle comprising a plurality of cyclodextrin moieties with a plurality of bridges comprising formula (I), (II), or (III).

[0010] In some embodiments, the present disclosure provides a method for purifying a fluid sample containing one or more contaminants, the method comprising contacting the fluid sample with a porous polymeric material or a supported porous polymeric material of the present disclosure, whereby at least 50% by weight of the total amount of the one or more contaminants in the fluid sample is adsorbed to the porous polymeric material.

[0011] In some embodiments, the present disclosure provides a method for removing one or more compounds from a fluid sample or determining the presence or absence of one or more compounds in a fluid sample, the method comprising: a) contacting the sample with a porous polymeric material or a supported porous polymeric material of the present disclosure for an incubation period; b) separating the porous polymeric material or the supported porous polymeric material from the sample after the incubation period; c) heating the porous polymeric material or the supported porous polymeric material separated in step b) or contacting the porous polymeric material or the supported porous polymeric material separated in step b) with a solvent, thereby releasing at least a portion of the compounds from the porous polymeric material or the supported porous polymeric material; d1) optionally isolating at least a portion of the compounds released in step c) or d2) determining the presence or absence of the compounds released in step c), wherein the presence of the one or more compounds correlates with the presence of the one or more compounds in the sample.

[0012] In some embodiments, the present disclosure provides articles of manufacture comprising the porous polymeric material or supported porous polymeric material of the present disclosure. [Brief description of the drawings]

[0013] [Figure 1] A comparison of the PFAS uptake capacity of polymers of the present disclosure at 0.5 hours (top) and 48 hours (bottom). [Diagram 2] Comparison of PFOA uptake (top) and PFOS uptake (bottom) between two choline chloride modified TFN-CDP polymers and one β-CD-TDI polymer. [Diagram 3] Shown are 1H NMR spectra of β-CD-TDI polymer (top) and β-CD (bottom). [Figure 4] 1 shows the change in the 1H NMR spectrum of the β-CD-TDI polymer upon addition of DO. [Diagram 5]1 shows a comparison of different β-CD-TDI polymers prepared with different molar equivalents of β-CD:TDI. [Figure 6-1] 1 shows a comparison of choline chloride modified β-CD-TDI polymers prepared with different molar equivalents of choline chloride. [Figure 6-2] 1 shows a comparison of choline chloride modified β-CD-TDI polymers prepared with different molar equivalents of choline chloride. [Figure 7] The uptake experiments of choline chloride-modified β-CD-TFN were performed using methylene blue (top) and methyl orange (bottom). [Figure 8] MO uptake isotherms for modified TFN-CDP polymers containing 1.5 (top) and 3.0 (middle) equivalents of choline chloride, and for unmodified TFN-CDP (bottom), are shown. Each dot represents an experimental data point, and each line is a curve fitted using the Langmuir model. [Figure 9] BPA uptake isotherms for modified TFN-CDP polymers containing 1.5 (top) and 3.0 (middle) equivalents of choline chloride, and unmodified TFN-CDP (bottom) are shown. Each dot represents an experimental data point, and each line is a curve fitted using the Langmuir model. [Figure 10] FIG. 1 shows the 1H NMR spectrum of a choline chloride modified β-CD-TDI polymer prepared with a molar equivalent ratio of 1:6:1 β-CD:TDI:choline chloride. [Figure 11] A comparison of choline chloride modified β-CD-TDI polymer and β-CD-TDI polymer is shown. [Figure 12] 1 shows a comparison between choline chloride modified β-CD-TDI polymers with different choline chloride loadings. [Figure 13] PFOA incorporation rate of choline chloride modified β-CD-TDI polymer is shown. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0014] All documents cited herein are incorporated by reference in their entirety for all purposes to the same extent as if each individual document was specifically and individually indicated to be incorporated by reference.

[0015] As used above, and throughout this disclosure, the following terms, unless otherwise indicated, shall be understood to have the following meanings: In the absence of a term, conventional terms known to those skilled in the art shall prevail.

[0016] As used herein, the terms "including," "containing," and "comprising" are used in their open, non-limiting sense.

[0017] The articles "a" and "an" are used in this disclosure to refer to one or to more than one (i.e., to at least one) of the grammatical object of the article. By way of example, "an element" means one element or more than one element.

[0018] The term "and / or" is used in this disclosure to mean either "and" or "or," unless otherwise indicated.

[0019] For more concise explanation, some of the quantitative expressions shown herein are not modified with the term "about". It should be understood that all amounts shown herein are intended to mean actual given values, whether or not the term "about" is explicitly used, and also intended to mean approximations to such given values ​​that are reasonably inferred based on ordinary skill in the art, including equivalent values ​​and approximations by experimental and / or measurement conditions to such given values. Whenever a yield is indicated as a percentage, such a yield is the same actual amount that can be obtained under specific stoichiometric conditions. The yield refers to the mass of the entity for which it is stated in relation to the maximum amount of the entity. Unless otherwise specified, concentrations given as percentages refer to mass ratios.

[0020] The terms adsorbent or adsorbing are used in reference to compositions or methods of the present disclosure to refer to solid materials described herein that remove contaminants or pollutants, typically, but not limited to, organic molecules, from a fluid medium such as a liquid (e.g., water) or gas (e.g., air or other commercially useful gases such as nitrogen, argon, helium, carbon dioxide, anesthetic gases, etc.). Such terms do not imply a particular physical mechanism (e.g., adsorption vs. absorption).

[0021] The term "cyclodextrin" includes any of the known cyclodextrins, such as unsubstituted cyclodextrins containing 6 to 12 glucose units, in particular α-cyclodextrin, β-cyclodextrin, γ-cyclodextrin and / or their derivatives and / or mixtures thereof. α-cyclodextrin is composed of 6 glucose units, β-cyclodextrin is composed of 7 glucose units and γ-cyclodextrin is composed of 8 glucose units, the glucose units being arranged in a donut-shaped ring. The specific linkage and conformation of the glucose units gives cyclodextrins a rigid cone-shaped molecular structure with a hollow interior of a specific volume. The "lining" of each internal cavity is formed by hydrogen atoms and glycosidic bridging oxygen atoms, which makes this surface correspondingly hydrophobic. The unique shape and physicochemical properties of the cavities allow the cyclodextrin molecule to absorb (form an inclusion complex) organic molecules or parts of organic molecules that fit into the cavities.

[0022] Unless otherwise specified, the term "crosslinker" or "crosslinking" or "linker" refers to a monomer that can react with or form a covalent bond between one or more cyclodextrins or polymers. For example, if the crosslinker reacts at the end of a polymer chain, it can covalently react with one cyclodextrin moiety of the polymer (e.g., via the glycosidic oxygen of the cyclodextrin). The crosslinker may or may not be capable of further reacting with other monomers or cyclodextrin units or polymer chains, for example, to extend the polymer chain or link two or more polymer chains together. For example, the crosslinker can be attached to one, two, three, four or more monomers or cyclodextrin units or polymers.

[0023] The term "cationic moiety" refers to a group bearing a positive charge (eg, +1, +2, etc.), such as ammonium, mono-, di-, or trialkylammonium, dialkylsulfonium, and trialkylphosphonium.

[0024] The term "anionic moiety" refers to groups that bear a negative charge (eg, -1, -2, etc.), such as phosphates, carboxylates, alkoxides, and sulfates.

[0025] As used herein, "alkyl" means a straight or branched saturated chain having from 1 to 10 carbon atoms. Representative saturated alkyl groups include, but are not limited to, methyl, ethyl, n-propyl, isopropyl, 2-methyl-1-propyl, 2-methyl-2-propyl, 2-methyl-1-butyl, 3-methyl-1-butyl, 2-methyl-3-butyl, 2,2-dimethyl-1-propyl, 2-methyl-1-pentyl, 3-methyl-1-pentyl, 4-methyl-1-pentyl, 2-methyl-2-pentyl, 3-methyl-2-pentyl, 4-methyl-2-pentyl, 2,2-dimethyl-1-butyl, 3,3-dimethyl-1-butyl, 2-ethyl-1-butyl, butyl, isobutyl, t-butyl, n-pentyl, isopentyl, neopentyl, n-hexyl, and the like, as well as longer alkyl groups such as heptyl, and octyl. Alkyl groups can be unsubstituted or substituted. An alkyl group having 3 or more carbon atoms may be linear or branched. As used herein, "lower alkyl" refers to an alkyl group having 1 to 6 carbon atoms.

[0026] The term "alkylene" refers to straight and branched chain alkylene groups. Typical alkylene groups include, for example, methylene (-CH-), ethylene (-CHCH-), propylene (-CHCHCH-), isopropylene (-CH(CH)CH-), n-butylene (-CHCHCHCH-), sec-butylene (-CH(CHCH)CH-), and the like.

[0027] The terms "hydroxyl" or "hydroxy" refer to an OH group.

[0028] It should also be noted that any carbon and heteroatoms with unsatisfied valences in the text, schemes, examples, and tables herein are assumed to have sufficient hydrogen atom(s) to satisfy the valences.

[0029] The term "halo" or "halogen" refers to fluorine, chlorine, bromine, or iodine.

[0030] The term "cyano" as used herein refers to a substituent having a carbon atom attached to a nitrogen atom by a triple bond, ie, C≡N.

[0031] The term "amine" or "amino" as used herein refers to a substituent having at least one nitrogen atom. Specifically included within the term "amino" are NH, -NH(alkyl) or alkylamino, -N(alkyl) or dialkylamino, amido, carboxamide, urea, and sulfamide substituents.

[0032] Unless expressly defined otherwise, the term "aryl" refers to a cyclic aromatic hydrocarbon group having one to three aromatic rings, including monocyclic or bicyclic groups such as phenyl, biphenyl, or naphthyl. When containing two aromatic rings (such as bicyclic), the aromatic rings of the aryl group may be bonded at one point (e.g., biphenyl) or fused (e.g., naphthyl). Furthermore, in the context of this disclosure, the term aryl is taken to refer to two aryl rings connected by a short linker such as -CH2-, CR2- (where R can be H, alkyl, etc.), -SO2-, -SO-, -NR- (where R can be H, alkyl, etc.), or -O-, e.g., aryl may refer to methylenediphenyl or oxybisphenyl, respectively. The aryl group may be optionally substituted with one or more substituents (e.g., 1 to 5 substituents) at any point of attachment. The substituents may themselves be optionally substituted. Additionally, when containing two fused rings, aryl groups as defined herein can have an unsaturated or partially saturated ring fused to a fully saturated ring. Exemplary ring systems of these aryl groups include, but are not limited to, phenyl, biphenyl, naphthyl, anthracenyl, phenalenyl, phenanthrenyl, indanyl, indenyl, tetrahydronaphthalenyl, tetrahydrobenzoannulenyl, and the like.

[0033] Unless otherwise specifically defined, "heteroaryl" means a monovalent monocyclic or polycyclic aromatic radical of 5 to 18 ring atoms containing one or more ring heteroatoms selected from N, O, or S, with the remaining ring atoms being C, or a polycyclic aromatic radical. Heteroaryl as defined herein also means a polycyclic (e.g., bicyclic) heteroaromatic group in which the heteroatoms are selected from N, O, or S. The aromatic radical is optionally substituted, independently, with one or more substituents described herein. The substituents are optionally selected from those which are also optionally substituted. Examples include, but are not limited to, benzothiophene, furyl, thienyl, pyrrolyl, pyridyl, pyrazinyl, pyrazolyl, pyridazinyl, pyrimidinyl, imidazolyl, isoxazolyl, oxazolyl, oxadiazolyl, pyrazinyl, indolyl, thiophen-2-yl, quinolyl, benzopyranyl, isothiazolyl, thiazolyl, thiadiazolyl, thieno[3,2-b]thiophene, Triazolyl, triazinyl, imidazo[1,2-b]pyrazolyl, furo[2,3-c]pyridinyl, imidazo[1,2-a]pyridinyl, indazolyl, pyrrolo[2,3-c]pyridinyl, pyrrolo[3,2-c]pyridinyl, pyrazolo[3,4-c]pyridinyl, benzimidazolyl, thieno[3,2-c]pyridinyl, thieno[2,3-c]pyridinyl, thieno[2,3-b]pyridinyl, benzothiazo Allyl, indolyl, indolinyl, indolinonyl, dihydrobenzothiophenyl, dihydrobenzofuranyl, benzofuran, chromanyl, thiochromanyl, tetrahydroquinolinyl, dihydrobenzothiazine, dihydrobenzoxanyl, quinolinyl, isoquinolinyl, 1,6-naphthyridinyl, benzo[de]isoquinolinyl, pyrido[4,3-b][1,6]naphthyridinyl, thieno[2,3-b] Pyrazinyl, quinazolinyl, tetrazolo[1,5-a]pyridinyl, [1,2,4]triazolo[4,3-a]pyridinyl, isoindolyl, pyrrolo[2,3-b]pyridinyl, pyrrolo[3,4-b]pyridinyl, pyrrolo[3,2-b]pyridinyl, imidazo[5,4-b]pyridinyl, pyrrolo[1,2-a]pyrimidinyl, tetrahydropyrrolo[1,2-a]pyrimidinyl, 3,4-dihydro-2H-1λ 2-pyrrolo[2,1-b]pyrimidine, dibenzo[b,d]thiophene, pyridin-2-one, furo[3,2-c]pyridinyl, furo[2,3-c]pyridinyl, 1H-pyrido[3,4-b][1,4]thiazinyl, benzoxazolyl, benzisoxazolyl, furo[2,3-b]pyridinyl, benzothiophenyl, 1,5-naphthyridinyl, furo[3,2-b]pyridine, [1,2,4]triazolo[1,5-a]pyridinyl, benzo[1,2,3]triazolyl, imidazo[1,2-a]pyrimidinyl, [1,2,4]triazolyl Examples of heteroaryl groups include azolo[4,3-b]pyridazinyl, benzo[c][1,2,5]thiadiazolyl, benzo[c][1,2,5]oxadiazole, 1,3-dihydro-2H-benzo[d]imidazol-2-one, 3,4-dihydro-2H-pyrazolo[1,5-b][1,2]oxazinyl, 4,5,6,7-tetrahydropyrazolo[1,5-a]pyridinyl, thiazolo[5,4-d]thiazolyl, imidazo[2,1-b][1,3,4]thiadiazolyl, thieno[2,3-b]pyrrolyl, 3H-indolyl, and derivatives thereof. Furthermore, when containing two fused rings, the heteroaryl groups defined herein may have an unsaturated or partially saturated ring fused to a fully saturated ring.

[0034] Numerical ranges used herein are intended to include consecutive integers unless otherwise indicated. For example, a range expressed as "from 0 to 5" is intended to include 0, 1, 2, 3, 4, and 5.

[0035] The present disclosure provides porous (e.g., microporous or mesoporous), generally high surface area cyclodextrin polymer materials (P-CDPs), as well as methods of making and using these materials. P-CDPs are composed of insoluble polymers of cyclodextrin, a macrocyclic compound of glucose, that are inexpensive and sustainably produced. The cyclodextrin polymers are crosslinked with linking groups as described herein. The cyclodextrin polymers are composed of cyclodextrin moieties that are derived from cyclodextrin. The cyclodextrin moieties can be derived from naturally occurring cyclodextrins (e.g., α-, β-, and γ-, which contain 6, 7, and 8 glucose units, respectively) or synthetic cyclodextrins. The cyclodextrin moieties have at least one -O- bond that is derived from an -OH group on the cyclodextrin from which the cyclodextrin moiety is derived. The cyclodextrin moiety can contain 3 to 20 glucose units (including all ranges between those values), and can have 3, 4, 5, 6, 7, 8, 9, 10, 11, 12 , 13, 14, 15, 16, 17, 18, 19, and 20 glucose units. In many embodiments, the cyclodextrin moiety is derived from starch and contains 6 to 9 glucose units. The polymeric material can contain two or more different cyclodextrin moieties. In certain embodiments, P-CDP is composed of an insoluble polymer of β-cyclodextrin (β-CD).

[0036] P-CDP may also include cyclodextrin derivatives or modified cyclodextrins. Derivatives of cyclodextrins are primarily composed of molecules in which some of the OH groups have been converted to OR groups. Cyclodextrin derivatives can have one or more additional moieties that provide additional functionality, such as desirable solubility behavior and affinity properties. Examples of suitable cyclodextrin derivative materials include methylated cyclodextrins (e.g., RAMEB, randomly methylated β-cyclodextrin), hydroxyalkylated cyclodextrins (e.g., hydroxypropyl-β-cyclodextrin and hydroxypropyl-γ-cyclodextrin), acetylated cyclodextrins (e.g., acetyl-γ-cyclodextrin), reactive cyclodextrins (e.g., chlorotriazinyl-β-CD), branched cyclodextrins (e.g., glucosyl-β-cyclodextrin and maltosyl-β-cyclodextrin), sulfobutyl-β-cyclodextrin, and sulfated cyclodextrin. For example, the cyclodextrin moiety further includes a moiety that binds (eg, specifically) a metal, such as arsenic, cadmium, copper, or lead.

[0037] P-CDP also includes cyclodextrin derivatives with short alkyl chains, such as methylated cyclodextrins and ethylated cyclodextrins, where R is a methyl or ethyl group; - those with hydroxy substituents such as hydroxypropyl cyclodextrin and / or hydroxyethyl cyclodextrin, where R is CH2CH2-OH; branched cyclodextrins such as maltose-linked cyclodextrin; cationic cyclodextrins such as those containing 2-hydroxy-3-(dimethylamino)propyl ether, where R is CH2-CH(OH)-CH2-N(CH3)2, which is cationic at low pH; + (CH3)3Cl -quaternary ammonium such as 2-hydroxy-3-(trimethylammonio)propyl ether chloride group; anionic cyclodextrins such as carboxymethyl cyclodextrin, sulfate cyclodextrin, and succinyl cyclodextrin; amphoteric cyclodextrins such as carboxymethyl / quaternary ammonium cyclodextrin; "Optimal Performances with Minimal Chemical Modification of Cyclodextrins", F. Diedaini-Pilard and B. Perly, The 7th International Cyclodextrin Symposium No. 6,881,712, including cyclodextrins in which at least one glucopyranose unit has a 3-6-anhydro-cyclomalto structure, e.g., mono-3-6-anhydrocyclodextrin, as disclosed in U.S. Patent No. 6,881,712 (the above references being incorporated by reference). Other cyclodextrin derivatives may include those disclosed in U.S. Patent No. 3,426,011, issued February 4, 1964 to Parmerter et al.; U.S. Patent Nos. 3,453,257, 3,453,258, 3,453,259, and 3,453,260, all in the name of Parmerter et al., issued July 1, 1969; U.S. Patent No. 3,459,731, issued August 5, 1969 to Gramera et al. U.S. Patent No. 3,553,191 to Parmerter et al., issued January 5, 1971; U.S. Patent No. 3,565,887 to Parmerter et al., issued February 23, 1971; U.S. Patent No. 4,535,152 to Szejtli, issued August 13, 1985; U.S. Patent No. 4,616,008 to Hirai et al., issued October 7, 1986; U.S. Patent No. 4,616,008 to Ogino et al., issued July 7, 1987 No. 4,678,598, issued Jan. 20, 1987 to Brandt et al.; U.S. Pat. No. 4,638,058, issued May 24, 1988 to Tsuchiyama et al., all of which are incorporated herein by reference.

[0038] In some embodiments, the present disclosure provides a compound of formula (I): [ka] a porous polymeric material comprising a plurality of cyclodextrins crosslinked with a plurality of bridges having During the ceremony, A is an aryl or heteroaryl moiety; Each R 1 is H, C1-C6 alkyl, C1-C3 haloalkyl, aryl, heteroaryl, -CF3, -SO3H, -CN, -NO2, -NH2, -NCO, -C(O)2R 3 , -C(O)N(R 3 -halogen; Each R 2 are independently H, -OH, -O-metal cation, alkyl, aryl, heteroaryl, -SH, -S-metal cation, -S-alkyl, -C(O)H, or -C(O)NH; Each R 3 are independently -H, -C1-C6 alkyl, -C1-C3 haloalkyl, aryl, -C(O)N(R a )(R b ), -C(O)R c , -CO2R c , -SO2N(R a )(R b ), or -SOR c And each R a and R b are independently H or C1-C6 alkyl; Each W is independently a bond, an alkylene group, an arylene group, a heteroarylene group, -O-arylene-, -(CH) a-Arylene-, -SO2-arylene-, -NH-arylene-, -S-arylene-, -O-heteroarylene-, -(CH2) a -Heteroarylene-, -SO2-heteroarylene-, -NH-heteroarylene-, -S-heteroarylene-, -(-O-(CH2) a -) x -, -(-NH-(CH2) a -) x -, -(-S-(CH2) a -) x -, [ka] wherein a is 0 to 100, x is 1 to 100, and each arylene or heteroarylene moiety may be substituted or unsubstituted; each Z is a cationic or anionic moiety; Each L is independently -O-, -S-, -N-, a C1 to C6 substituted or unsubstituted alkyl group. olefin, C1-C3 haloalkylene, [ka] is a linking moiety selected from the group consisting of A' is a covalent bond to A, Z' is a covalent bond to Z; *teeth, [ka] is a covalent bond to [ka] is the point of attachment to multiple cyclodextrin carbon atoms, x is 0 to 8; y1 is 1 to 4; y2 is 1 to 4; y3 is 0 to 4.

[0039] Each Z is a cationic moiety or an anionic moiety. For example, in some embodiments, each Z is a cationic moiety. In certain embodiments, each cationic moiety is independently -N(R 3 )3 + , -P(R 3 )3 + , -S(R 3 )2 + , or -heteroaryl + And each R 3 are independently -H, -C1-C6 alkyl, -C1-C3 haloalkyl, -aryl, -C(O)N(R a )(R b ), -C(O)R c , -CO2R c , -SO2N(R a )(R b ), or -SOR c And each R a and R b is independently H, or C1-C6 alkyl. For example, in some embodiments, each cationic moiety is -N(R 3 )3 + And each R 3 is H, or C1-C6 alkyl. Thus, in some embodiments, each cationic moiety is -N(Me)3 + or -NH3 + In some embodiments, each cationic moiety is -N(Me)3 + In some embodiments, each cationic moiety is independently -heteroaryl. + In the context of this disclosure, a variety of charged heteroaryls are contemplated and will be readily apparent to one of ordinary skill in the art. For example, in some embodiments, -heteroaryl + may refer to pyridinium, pyrrolidinium, imidazolium, triazolium, tetrazolium, etc. In some embodiments, each Z is an anionic moiety. In certain embodiments, each anionic moiety is [ka] And each R 3 is as defined above.

[0040] According to certain embodiments of the present disclosure, each W is independently a bond, an alkylene group (e.g., C1-C 10 , C 10 ~C 20 , or C 20 ~C 100 ), arylene group, heteroarylene group, -O-arylene-, -(CH2) a -Arylene-, -SO2-arylene-, -NH-arylene-, -S-arylene-, -O-heteroarylene-, -(CH2) a -Heteroarylene-, -SO2-heteroarylene-, -NH-heteroarylene-, -S-heteroarylene-, -(-O-(CH2) a -) x -, -(-NH-(CH2) a -) x - or -(-S-(CH2) a -) x-, a is 0 to 100, x is 1 to 100, and each arylene or heteroarylene moiety may be substituted or unsubstituted. The term "arylene" refers to a divalent group derived from an aryl group (including phenyl, biphenyl, naphthyl, etc., as described herein) by removing hydrogen atoms from two ring carbons. For example, an arylene can include a phenyl with the two valence electrons positioned in the ortho, meta, or para orientation. In the case of a polycyclic arylene, the two valence electrons can be in the same ring or different rings. An arylene can be derived from any aromatic ring as described herein and can be substituted or unsubstituted. Similarly, the term "heteroarylene" refers to a divalent group derived from a heteroaryl group (including furyl, pyridyl, etc., as described herein) by removing hydrogen atoms from two ring atoms (which can be carbons or heteroatoms). The valence electrons can be in the same ring or different rings (in the case of a polycyclic heteroaromatic) and can be on any two ring atoms. Heteroarylene can be derived from any heteroaromatic ring described herein and can be substituted or unsubstituted. Thus, in some embodiments, each W is a bond (i.e., a covalent bond). In other embodiments, each W is an alkylene group. For example, each W can be methylene (-CH-), ethylene (-CHCH-), propylene (-CHCHCH-), isopropylene (-CH(CH)CH-), n-butylene (-CHCHCHCH-), sec-butylene (-CH(CHCH)CH-), and the like. In some embodiments, each W is methylene (-CH-). In some embodiments, each W is an arylene group (phenylene). In some embodiments, each W is a heteroarylene group (furyl, pyridyl). In some embodiments, each W is -O-arylene-(-O-phenylene). In some embodiments, each W is -(CH) aIn some embodiments, each W is -arylene-(-CH2-phenylene). In some embodiments, each W is -SO2-arylene-(-SO2-phenylene). In some embodiments, each W is -NH-arylene-(-NH-phenylene). In some embodiments, each W is -S-arylene-(-S-phenylene). In some embodiments, each W is a heteroarylene group (furylene, pyridylene). In some embodiments, each W is -O-heteroarylene-(-O-pyridinylene). In some embodiments, each W is -(CH2) a In some embodiments, each W is -SO2-heteroarylene-(-SO2-pyridinylene). In some embodiments, each W is -NH-heteroarylene-(-NH-pyridinylene). In some embodiments, each W is -S-heteroarylene-(-S-pyridinylene). In some embodiments, W is -(O-CH2-CH2) x In some embodiments, W is -O-CH-CH-. In some embodiments, W is [ka] where A' is a covalent bond to A and Z' is a covalent bond to Z. In some embodiments, W is [ka] It is.

[0041] In some embodiments, each of -WZ taken together is -O-CH2-CH2-N(R)3 + In some embodiments, each of -WZ taken together forms -O-CH2-CH2-N(Me)3 + In some embodiments, each of -WZ, taken together, forms [ka] Form.

[0042] In some embodiments, each L is a linking moiety. In some embodiments, each L is independently -O-, -S-, -N-, [ka] where A' is a covalent bond to A and * is a linking moiety selected from the group consisting of: [ka] (representing the points of attachment to multiple cyclodextrin carbon atoms, as described herein). In some embodiments, each L is independently -O-. In certain embodiments, L is independently [ka] Or -O-, the oxygen atom can be a glycosidic oxygen from a plurality of cyclodextrin atoms of the porous polymeric material of the present disclosure. For example, in some embodiments, when each L is independently -O-, the oxygen atom is a glycosyl oxygen from a plurality of cyclodextrin atoms of the porous polymeric material of the present disclosure.

[0043] In some embodiments, A is an aryl or heteroaryl moiety. In some embodiments, A is an aryl moiety. For example, A can be phenyl, biphenyl, naphthyl, anthracenyl, phenalenyl, phenanthrenyl, indanyl, indenyl, tetrahydronaphthalenyl, or tetrahydrobenzoannulenyl. In some embodiments, A is a heteroaryl moiety. For example, A can be benzothiophene, furyl, thienyl, pyrrolyl, pyridyl, pyrazinyl, pyrazolyl, pyridazinyl, pyrimidinyl, imidazolyl, isoxazolyl, oxazolyl, oxadiazolyl, pyrazinyl, indolyl, thiophen-2-yl, quinolyl, benzopyranyl, isothiazolyl, thiazolyl, thiadiazolyl, thieno[3,2-b]thiophene, triazolyl, triazinylidene. imidazo[1,2-b]pyrazolyl, furo[2,3-c]pyridinyl, imidazo[1,2-a]pyridinyl, indazolyl, pyrrolo[2,3-c]pyridinyl, pyrrolo[3,2-c]pyridinyl, pyrazolo[3,4-c]pyridinyl, benzimidazolyl, thieno[3,2-c]pyridinyl, thieno[2,3-c]pyridinyl, thieno[2,3-b]pyridinyl, benzothiazolyl, indolyl , indolinyl, indolinonyl, dihydrobenzothiophenyl, dihydrobenzofuranyl, benzofuran, chromanyl, thiochromanyl, tetrahydroquinolinyl, dihydrobenzothiazine, dihydrobenzoxanyl, quinolinyl, isoquinolinyl, 1,6-naphthyridinyl, benzo[de]isoquinolinyl, pyrido[4,3-b][1,6]naphthyridinyl, thieno[2,3-b]pyraziny quinazolinyl, tetrazolo[1,5-a]pyridinyl, [1,2,4]triazolo[4,3-a]pyridinyl, isoindolyl, pyrrolo[2,3-b]pyridinyl, pyrrolo[3,4-b]pyridinyl, pyrrolo[3,2-b]pyridinyl, imidazo[5,4-b]pyridinyl, pyrrolo[1,2-a]pyrimidinyl, tetrahydropyrrolo[1,2-a]pyrimidinyl, 3,4-dihydro-2H-1λ 2-pyrrolo[2,1-b]pyrimidine, dibenzo[b,d]thiophene, pyridin-2-one, furo[3,2-c]pyridinyl, furo[2,3-c]pyridinyl, 1H-pyrido[3,4-b][1,4]thiazinyl, benzoxazolyl, benzisoxazolyl, furo[2,3-b]pyridinyl, benzothiophenyl, 1,5-naphthyridinyl, furo[3,2-b]pyridine, [1,2,4]triazolo[1,5-a]pyridinyl, benzo[1,2,3]triazolyl, imidazo[1,2-a]pyrimidinyl, [1,2,4 ]triazolo[4,3-b]pyridazinyl, benzo[c][1,2,5]thiadiazolyl, benzo[c][1,2,5]oxadiazole, 1,3-dihydro-2H-benzo[d]imidazol-2-one, 3,4-dihydro-2H-pyrazolo[1,5-b][1,2]oxazinyl, 4,5,6,7-tetrahydropyrazolo[1,5-a]pyridinyl, thiazolo[5,4-d]thiazolyl, imidazo[2,1-b][1,3,4]thiadiazolyl, thieno[2,3-b]pyrrolyl, or 3H-indolyl. In some embodiments, A is selected from the group consisting of phenyl, naphthyl, pyridyl, benzofuranyl, pyrazinyl, pyridazinyl, pyrimidinyl, triazinyl, quinoline, benzoxazole, benzothiazole, 1H-benzimidazole, isoquinoline, quinazoline, quinoxaline, pyrrole, indole, biphenyl, pyrenyl, and anthracenyl. In some embodiments, A is an aryl or heteroaryl ring system as described in U.S. Patent No. 9,855,545, herein incorporated by reference in its entirety.

[0044] In some embodiments, A is the polymerization product of commercially available diisocyanates. For example, in some embodiments, A is a polymerization product of commercially available aryl diisocyanates, including, but not limited to, 2,4-toluene diisocyanate, 2,6-toluene diisocyanate, 4,4'-methylene diphenyl diisocyanate, 2,4'-methylene diphenyl diisocyanate, 1,3-bis(isocyanatomethyl)benzene, 1,3-bis(1-isocyanato-1-methylethyl)benzene, 3,3'-dichloro-4,4'-diisocyanato-1,1'-biphenyl, 3,3'-dimethyl-4,4'-biphenylene diisocyanate, 4,4'-oxybis(phenylisocyanate), 1,3-phenylene diisocyanate, 1,4-phenylene diisocyanate, 4-chloro-6-methyl-1,3-phenylene diisocyanate, and 1-chloromethyl-2,4-diisocyanatobenzene. [ka] where the wavy line represents any of the substituents attached to A as defined herein. In some embodiments, A is [ka] where the wavy line represents any of the substituents attached to A as defined herein. In some embodiments, A is [ka] where the wavy line represents any of the substituents attached to A as defined herein, and the -Me, -Cl, and -CH-Cl groups attached to the aryl ring of the above structure are R 1 In some embodiments, A corresponds to the -CH- and -C(Me)- groups attached to the aryl ring, and the -CH- and -C(Me)- groups correspond to the L group. [ka] where the wavy line represents any of the substituents attached to A as defined herein, and the -Me and -Cl groups attached to the aryl ring in the above structure are R 1 Corresponding to the group.

[0045] The porous polymeric material of the present disclosure includes a plurality of cyclodextrins having a plurality of bridges having formula (I). The plurality of cyclodextrins of the present disclosure may be any cyclodextrin containing 6 to 12 glucose units. For example, in some embodiments, the plurality of cyclodextrins of the present disclosure are selected from the group consisting of α-cyclodextrin, β-cyclodextrin, γ-cyclodextrin, and combinations thereof. In some embodiments, each cyclodextrin is a β-cyclodextrin.

[0046] R of multiple bridges having formula (I) 1 The group is each R 1 is H, C1-C6 alkyl, C1-C3 haloalkyl, aryl, heteroaryl, -CF3, -SO3H, -CN, -NO2, -NH2, -NCO, -C(O)2R 3 , -C(O)N(R 3 In certain embodiments, each R 1 is H, C1-C6 alkyl, C1-C3 haloalkyl, aryl, heteroaryl, -CF3, -SO3H, -CN, -NO2, -NH2, -NCO, -C(O)2R 3 , -C(O)N(R 3 In certain embodiments, 0 to 8 R on the bridges having formula (I) are independently selected from the group consisting of: -, ... 1 For example, 0, 1, 2, 3, 4, 5, 6, 7, or 8 R 1 A group is present on each individual bridge having formula (I). 1 , R 2It is understood that any position of A that is not substituted with -WZ, or -L- is unsubstituted or has one or more H atoms required to satisfy the valence of that position. As will be appreciated by those of skill in the art, each R of the individual bridges of formula (I) 1 The number of groups can vary throughout the porous polymeric materials of the present disclosure. For example, R 1 is -F and the polymerized porous material of the present invention is exposed to a reactant capable of displacement (e.g., choline chloride), the -F groups on some crosslinks will be displaced, while on other crosslinks the -F groups may not react because they are effectively shielded from the reactant. Thus, multiple linking groups of formula (I) may be present in the porous polymeric material of the present disclosure, with each individual linking group independently being selected from 0 to 8 (e.g., 1, 2, or 3) R 1 It can have a group.

[0047] In some embodiments, the porous polymeric material of the present disclosure has, on average, a R expressed as a decimal 1 , R 2 The fraction of substituents can be calculated by dividing the total number of such groups by the total number of crosslinks in the porous polymeric material. For example, if half of the crosslinks are -O-CH2-CH2-N(Me)3, then the fraction of the crosslinks in the porous polymeric material is -O-CH2-CH2-N(Me)3. + When functionalized with a group (e.g., when W is -O-CH2-CH2- and Z is -N(Me)3), there is -O-CH2-CH2-N(Me)3 corresponding to -WZ per bridging group. + The average number of groups (or decimal points) is 0.5. 1For the formula, decimals of such groups are about 0, about 0.1, about 0.2, about 0.3, about 0.4, about 0.5, about 0.6, about 0.7, about 0.8, about 0.9, about 1.0, about 1.1, about 1.2, about 1.3, about 1.4, about 1.5, about 1.6, about 1.7, about 1.8, about 1.9, about 2.0, about 2.1, about 2.2, about 2.3, about 2.4, about 2.5, about 2.5, about 2.7, about 2.8, about 2.9, about 3.0, about 3.1, about 3.2, about 3.3, about 3.4, about 3.5, about 3.6, about 3.7, about 3.8, about 3.9, about 4.0, about 4.1, about 4.2, about 4.3, about 4.4, about 4.5, about 4.6, about 4.7, about 4,8. about 4.9, about 5.0, about 5.1, about 5.2, about R includes values ​​of about 5.3, about 5.4, about 5.5, about 5.6, about 5.7, about 5.8, about 5.9, about 6.0, about 6.1, about 6.2, about 6.3, about 6.4, about 6.5, about 6.6, about 6.7, about 6.8, about 6.9, about 7.0, about 7.1, about 7.2, about 7.3, about 7.4, about 7.5, about 7.6, about 7.7, about 7.8, about 7.9, or about 8.0, including all ranges between any of these values. 2For , decimals of such groups include about 0, about 0.1, about 0.2, about 0.3, about 0.4, about 0.5, about 0.6, about 0.7, about 0.8, about 0.9, about 1.0, about 1.1, about 1.2, about 1.3, about 1.4, about 1.5, about 1.6, about 1.7, about 1.8, about 1.9, about 2.0, about 2.1, about 2.2, about 2.3, about 2.4, about 2.5, about 2.5, about 2.7, about 2.8, about 2.9, about 3.0, about 3.1, about 3.2, about 3.3, about 3.4, about 3.5, about 3.6, about 3.7, about 3.8, about 3.9, or about 4.0, including all ranges between any of these values. For -WZ, decimals of such groups include about 1.0, about 1.1, about 1.2, about 1.3, about 1.4, about 1.5, about 1.6, about 1.7, about 1.8, about 1.9, about 2.0, about 2.1, about 2.2, about 2.3, about 2.4, about 2.5, about 2.5, about 2.7, about 2.8, about 2.9, about 3.0, about 3.1, about 3.2, about 3.3, about 3.4, about 3.5, about 3.6, about 3.7, about 3.8, about 3.9, or about 4.0, including all ranges between any of these values. For -L-, decimals of such groups include about 1.0, about 1.1, about 1.2, about 1.3, about 1.4, about 1.5, about 1.6, about 1.7, about 1.8, about 1.9, about 2.0, about 2.1, about 2.2, about 2.3, about 2.4, about 2.5, about 2.5, about 2.7, about 2.8, about 2.9, about 3.0, about 3.1, about 3.2, about 3.3, about 3.4, about 3.5, about 3.6, about 3.7, about 3.8, about 3.9, or about 4.0, including all ranges between any of these values.

[0048] Each R 2 is independently H, -OH, -O-metal cation, alkyl, aryl, heteroaryl, -SH, -S-metal cation, -S-alkyl, -C(O)H, or -C(O)NH. 2 is H. In some embodiments, each R 2 In some embodiments, each R 2 is an -O-metal cation. In some embodiments, each R 2 is alkyl. In some embodiments, each R 2is aryl (e.g., substituted or unsubstituted phenyl or naphthyl). In some embodiments, each R 2 is heteroaryl (e.g., a substituted or unsubstituted 5- or 6-membered heteroaryl ring having 1, 2, or 3 ring heteroatoms selected from the group consisting of O, S, or N). In some embodiments, each R 2 In some embodiments, each R 2 is an -S-metal cation. In some embodiments, each R 2 According to an embodiment of the present disclosure, one, two, three, or four R 2 For example, 0, 1, 2, 3, or 4 R 2 As will be appreciated by those of skill in the art, each R of each of the individual linking groups having formula (I) may be present on the bridges having formula (I). 2 The number of groups can vary for each individual linking group throughout the porous polymeric materials of the present disclosure. Thus, multiple linking groups of formula (I) can be present in the porous polymeric materials of the present disclosure, with each individual linking group independently having, for example, 0, 1, 2, 3, or 4 R 2 One or more R 2 When groups are present on more than one linking group of formula (I), each R 2 The groups can be the same or different. For example, in some embodiments, one or more R 2 The group is an -O-metal cation and one or more R 2 The group is -OH.

[0049] Each R 3 are independently -H, -C1-C6 alkyl, -C1-C3 haloalkyl, aryl, -C(O)N(R a )(R b ), -C(O)R c , -CO2R c , -SO2N(R a )(R b ), or -SOR c And each R a and R bis independently H, or C1-C6 alkyl. In some embodiments, each R 3 In some embodiments, each R 3 is H. 3 When is aryl, the aryl can be, for example, substituted or unsubstituted phenyl or naphthyl.

[0050] In certain embodiments, x is 1 to 4. For example, x can be 1, 2, 3, or 4. In some embodiments, x is 1 or 2, and R 1 is -F.

[0051] In certain embodiments, y1 is 1 to 4. For example, y1 can be 1, 2, 3, or 4. In some embodiments, y1 is 1 to 2.

[0052] In certain embodiments, y2 is 1 or 2.

[0053] In certain embodiments, y3 is 0 or 1.

[0054] In certain embodiments, the porous polymeric material of the present disclosure has formula (II): [ka] a plurality of cyclodextrins crosslinked by a plurality of bridges having the formula: During the ceremony, y2 is 1 or 2; x is 1 or 2. In some embodiments, y2 is 2 and x is 1. In some embodiments, each cyclodextrin is a β-cyclodextrin.

[0055] In certain embodiments, the porous polymeric material of the present disclosure has formula (III): [ka] and a plurality of linkers of

[0056] Wherein, one R 4 is -H and one R 4 is -Me. In some embodiments, each cyclodextrin is a β-cyclodextrin.

[0057] In various embodiments, the porous polymeric materials of the present disclosure are prepared by crosslinking cyclodextrins of the same structure with a crosslinker of the same structure. In some embodiments, the porous polymeric materials of the present disclosure are prepared by crosslinking cyclodextrins of the same structure with two, three, four, or more different crosslinkers. In various embodiments, the porous polymeric materials of the present disclosure are prepared by crosslinking two, three, or four different cyclodextrins (i.e., having different structures) with a crosslinker of the same structure. In some embodiments, the porous polymeric materials of the present disclosure are prepared by crosslinking two, three, or four different cyclodextrins with two, three, four, or more different crosslinkers. The crosslinking agents are prepared by crosslinking with different crosslinking agents.

[0058] In some embodiments, some of the crosslinks of the porous polymeric material do not include a cationic or anionic moiety (i.e., corresponding to the group "Z" in formula (I)). In such embodiments, the porous polymeric material includes a plurality of crosslinkers of formula (I) and a plurality of crosslinkers having a structure similar to the crosslinkers of formula (I) except that there is no cationic or anionic moiety corresponding to the group "Z". Thus, for example, such crosslinkers lacking cationic or anionic moieties can have any of the crosslinker structures described in U.S. Pat. No. 10,086,360, incorporated herein by reference for all purposes, such as the following structure (a): [ka] Or the following structure (b): [ka] or multiple crosslinkers of a combination of structures (a) and (b), where x in structure (b) is 0, 1, 2, 3, or 4. In such embodiments of porous polymeric materials having crosslinkers of structure (a) and / or structure (b), such materials also include a charged crosslinker of formula (I) as described herein.

[0059] In yet another embodiment, the porous polymeric material of the present disclosure has the following structure (c): [ka] (In the formula, X - is Cl - The present invention includes a plurality of cationic crosslinkers, each of which is a pharma- ceutically acceptable anionic counterion such as

[0060] In yet another embodiment, the porous polymeric material of the present disclosure has the following structure (d): [ka] (In structure (d), x is 0, 1, 2, 3, or 4; X - is Cl - The present invention includes a plurality of cationic crosslinkers, each of which is a pharma- ceutically acceptable anionic counterion such as

[0061] In yet another embodiment, the porous polymeric material of the present disclosure comprises a plurality of cationic crosslinkers of structure (c) and a plurality of cationic crosslinkers of structure (d). Any of the crosslinkers of the present disclosure having aromatic halide groups can be modified to provide charged moieties, for example, by reaction with choline chloride under appropriate conditions as described herein.

[0062] In other embodiments, the porous polymeric material of the present disclosure has the following structure (e): [ka] The present invention includes a plurality of anionic crosslinkers.

[0063] Alternatively, the cationic counterion of structure (e) (Na + (denoted as H + or K + The counterion may be any other pharma- ceutically acceptable cationic counterion, such as, but not limited to,

[0064] In yet other embodiments, the porous polymeric material of the present disclosure has the following structure (f): [ka] (f) wherein x is 0, 1, 2, 3, or 4.

[0065] In yet another embodiment, the porous polymeric material of the present disclosure comprises a plurality of columns of structure (e). The crosslinker comprises a thionic crosslinker and a plurality of cationic crosslinkers of structure (f).

[0066] In some embodiments, the present disclosure provides a porous polymeric material comprising a plurality of cyclodextrin moieties crosslinked by one or more polyisocyanates. In some embodiments, the plurality of cyclodextrins is β-cyclodextrin. In some embodiments, the one or more polyisocyanates are aryl diisocyanates, including, but not limited to, 2,4-toluene diisocyanate, 2,6-toluene diisocyanate, 4,4'-methylene diphenyl diisocyanate, 2,4'-methylene diphenyl diisocyanate, 1,3-bis(isocyanatomethyl)benzene, 1,3-bis(1-isocyanato-1-methylethyl)benzene, 3,3'-dichloro-4,4'-diisocyanato-1,1'-biphenyl, 3,3'-dimethyl-4,4'-biphenylene diisocyanate, 4,4'-oxybis(phenylisocyanate), 1,3-phenylene diisocyanate, 1,4-phenylene diisocyanate, 4-chloro-6-methyl-1,3-phenylene diisocyanate, and 1-chloromethyl-2,4-diisocyanatobenzene, and combinations thereof. In some embodiments, the aryl diisocyanate is 2,4-toluene diisocyanate. In some embodiments, the one or more polyisocyanates are aliphatic diisocyanates, including, but not limited to, 4,4'-diisocyanato-methylene dicyclohexane (HMDI), hexamethylene diisocyanate (HDI), isophorone diisocyanate (IPDI), L-lysine diisocyanate (LDI), trimethylhexamethylene diisocyanate (TMDI), 1,3-bis(isocyanatomethyl)cyclohexane, 1,4-diisocyanatobutane, trimethyl-1,6-diisocyanatohexane, 1,6-diisocyanato-2,2,4-trimethylhexane, trans-1,4-cyclohexylene diisocyanate, 1,8-diisocyanatooctane, 1,12-diisocyanatododecane, and combinations thereof. In some embodiments, the plurality of cyclodextrins is β-cyclodextrin and the one or more polyisocyanates is 2,4-toluene diisocyanate. In some embodiments, the porous polymeric material is about 10 m.2 / g~2000m 2 / g. For example, in some embodiments, the porous polymeric material has a Brunauer-Emmett-Teller (BET) surface area of ​​about 10 m 2 / g, 20m 2 / g, 30m 2 / g, 40m 2 / g, 50m 2 / g, 75m 2 / g, 100m 2 / g, 150m 2 / g, 200m 2 / g, 250m 2 / g, 300m 2 / g, 350m 2 / g, 400m 2 / g, 450m 2 / g, 500m 2 / g, 550m 2 / g, 600m 2 / g, 650m 2 / g, 700m 2 / g, 750m 2 / g, 800m 2 / g, 850m 2 / g, 900m 2 / g, 950m 2 / g, 1000m 2 / g, 1050m 2 / g, 1100m 2 / g, 1150m 2 / g, 1200m 2 / g, 1250m 2 / g, 1300m 2 / g, 1350m 2 / g, 1400m 2 / g, 1450m 2 / g, 1500m 2 / g, 1550m 2 / g, 1600m 2 / g, 1650m 2 / g, 1700m 2 / g, 1750m 2 / g, 1800m 2 / g, 1850m 2 / g, 1900m 2 / g, 1950m 2 / g~about 2000m2 / g BET surface area, including all integers and ranges between these values. In some embodiments, the porous polymeric material has an amine content of about 0 mmol / g to about 1.0 mmol / g. In some embodiments, the porous polymeric material has an amine content of about 0.1 mmol / g to about 1.0 mmol / g. In some embodiments, the porous polymeric material has an amine content of about 0.15 mmol / g to about 0.35 mmol / g. For example, in some embodiments, the amine content is about 0.15 mmol / g, about 0.16 mmol / g, about 0.17 mmol / g, about 0.18 mmol / g, about 0.19 mmol / g, about 0.20 mmol / g, about 0.21 mmol / g, about 0.22 mmol / g, about 0.23 mmol / g, about 0.24 mmol / g, about 0.25 mmol / g, about 0.26 mmol / g, about 0.27 mmol / g, about 0.28 mmol / g, about 0.29 mmol / g, about 0.30 mmol / g, about 0.31 mmol / g, about 0.32 mmol / g, about 0.33 mmol / g, about 0.34 mmol / g, and about 0.35 mmol / g, including all ranges between these values. Without being bound to any particular theory, it has been discovered that by using neat CD (i.e., undried) in the polymer synthesis, the resulting polymer has a higher amine content than similar polymers described in the prior art, resulting in a higher affinity for certain trace pollutants, such as PFAS.

[0067] In certain embodiments, the molar ratio of the cyclodextrin to the linking group of formula (I), (II), or (III) ranges from about 1:1 to about 1:X, where X is three times the average number of glucose subunits in the cyclodextrin. In certain embodiments, the molar ratio of the cyclodextrin to the linking group of formula (I), (II), or (III) is about 1:6. In certain embodiments, the molar ratio of the cyclodextrin to the linking group of formula (I), (II), or (III) is about 1:5. In certain embodiments, the molar ratio of the cyclodextrin to the linking group of formula (I), (II), or (III) is about 1:4. In certain embodiments, the molar ratio of the cyclodextrin to the linking group of formula (I), (II), or (III) is about 1:3. In certain embodiments, the molar ratio of the cyclodextrin to the linking group of formula (I), (II), or (III) is about 1:2. In various embodiments, the molar ratio of cyclodextrin moieties to aryl bridging moieties is from about 1:1 to about 1:24, including about 1:1, about 1:1.5, about 1:2, about 1:2.5, about 1:3, about 1:3.5, about 1:4, about 1:4.5, about 1:5, about 1:5.5, about 1:6, about 1:6.5, about 1:7, about 1:7.5, about 1:8, about 1:8.5, about 1:9, about 1:9.5, about 1:10, about 1:10.5, about 1:11, about 1:11.5, about 1:1 2, about 1:12.5, about 1:13, about 1:13.5, about 1:14, about 1:14.5, about 1:15, about 1:15.5, about 1:16, about 1:16.5, about 1:17, about 1:17.5, about 1:18, about 1:18.5, about 1:19, about 1:19.5, about 1:20, about 1:20.5, about 1:21, about 1:21.5, about 1:22, about 1:22.5, about 1:23, about 1:23.5, or about 1:24, including all ratio ranges between these values. In one embodiment, the molar ratio of cyclodextrin moieties to aryl bridging moieties is from about 1:2.5 to about 1:10.

[0068] In some embodiments, the composition according to the present disclosure comprises one or more porous polymeric materials of the present disclosure and one or more support materials, where the porous polymeric materials are bonded (e.g., covalently bonded, adhesively, or mechanically bonded as described herein) to the support materials. For example, in some embodiments, the composition comprises a porous polymeric material comprising a plurality of cyclodextrins crosslinked by a plurality of bridges having formula (I), and / or (II), and / or (III). Examples of support materials include cellulose (e.g., cellulose fibers), activated carbon, graphene oxide, and carbon-based materials such as oxidized carbon materials, silica, alumina, natural or synthetic polymers, and natural or synthetic polymers modified to include surface hydroxyl groups. Those skilled in the art will recognize any material that has suitable mechanical or other properties to function as a support and can be covalently bonded to the porous polymeric material or can function as a suitable support material when the porous polymeric material is adhesively bonded to the support by a suitable binder material. In one embodiment, the composition is in the form of a membrane or column packing. In one embodiment, the support is a fiber (e.g., cellulose, nylon, polyolefin, or polyester fiber). In one embodiment, the substrate is a porous particulate material (e.g., porous silica and porous alumina). In one embodiment, the substrate is a woven or nonwoven fabric. In one embodiment, the substrate is a garment (such as a protective garment) or a surgical or medical drape, dressing, or sanitary product.

[0069] In some embodiments, P-CDPs can be grafted or bonded (e.g., chemically or mechanically bonded) onto a support to provide an adsorbent with well-controlled particle size and morphology to provide ideal flow characteristics. The term "mechanically bonded" refers to The term refers to bonds formed between two materials by pressure, ultrasonic bonding, and / or other mechanical bonding processes that do not involve the intentional application of heat, such as mechanical entanglement. Physical entanglement and coating of microfibrils to hold micron-sized particulate matter in place are representative examples of mechanical bonds. The term mechanical bonds does not include bonds formed using adhesives or chemical grafting. In some embodiments, P-CDP can be grafted or bonded (e.g., chemically or mechanically bonded) onto a support to provide an adsorbent whose particle size and morphology are further manipulated (e.g., by granulation or milling) to provide particles with well-controlled particle size and morphology to provide ideal flow characteristics.

[0070] P-CDP support complexes can be prepared by a variety of methods, including conventional grafting methods. As used herein, the term "grafting" refers to covalently attaching P-CDP to a substrate surface by a coupling reaction between one or more functional groups on the P-CDP and one or more functional groups on the substrate. In some embodiments, grafting includes the "in situ" process described herein, in which a cyclodextrin, a linking group of the present disclosure, and a substrate having a surface-bound nucleophilic species (e.g., hydroxyl) are reacted with each other, and the linking group of the present disclosure reacts with the hydroxyl group of the cyclodextrin and the surface nucleophilic species of the substrate to form a P-CDP partially attached to the substrate via one or more linking groups of the present disclosure. Substrates having surface-bound nucleophilic species include, but are not limited to, hydroxyl (such as microcrystalline cellulose), amines, phosphines, and thiols.

[0071] In some embodiments, the "grafted" P-CDP support composite is prepared by first synthesizing P-CDP in a dedicated chemical reactor with appropriate control of reaction conditions and material purification to produce optimized P-CDP particles. The P-CDP is then chemically reacted with an appropriately functionalized substrate. For example, a substrate functionalized with a carboxylic acid group (or its activated form, such as an acid halide, anhydride, etc., known in the art) can react with one or more hydroxyls on the P-CDP to form an ester bond with the substrate. Alternatively, the P-CDP can be appropriately functionalized by subsequent modification of the P-CDP (e.g., by selection of a functionalized cyclodextrin as described herein) so that it can react with an appropriate functional group on the substrate. Any suitable reaction chemistry may be contemplated, such as reaction of carboxylic acids (and their derivatives) with hydroxyls to form ester bonds, reaction of carboxylic acids (and their derivatives) with amine groups to form amide bonds, reaction of isocyanates with alcohols to form urethanes, reaction of isocyanates with amines to form ureas, reaction of cyclic carbonates with amines to form urethanes, reaction of thiols with alkenes or alkynes to form thioethers, reaction of epoxides with amine groups, photochemical reaction of acrylates, methacrylates, thiols, etc. with olefins. The reactive functional groups described herein may be present on either the P-CDP or the substrate, provided that the reaction forms a covalent bond between the substrate and the P-CDP. For example, in the case of reactive functional groups of hydroxyl and carboxylic acid (which form an ester bond after reaction), the hydroxyl group may be present on the P-CDP and the carboxyl group may be present on the substrate (or vice versa).

[0072] In other embodiments, the substrate can be coated with a "primer" having the reactive functional groups described above. The primer can be attached to the surface of the substrate and reacted under appropriate conditions with an appropriately functionalized P-CDP to form a covalent bond between the P-CDP and the primer.

[0073] P-CDP particles can be engineered to achieve a particular particle size. In some embodiments, P-CDP is produced in the form of crosslinked particles that may require further particle size reduction. The P-CDP is then mixed with water (e.g., to form a stable dispersion or slurry or to provide optimal flow characteristics). A variety of means, such as grinding or milling, can be used to reduce the particle size of the P-CDP, as will be readily apparent to one skilled in the art. Grinding and milling can be used to create small particles, less than 1 micron in size. Common milling procedures can be used by one skilled in the art, and include both wet and dry milling. Milling can be used in a variety of ways, including, but not limited to, ball mills, autogenous mills, SAG mills, pebble mills, rod mills, bar stone mills, tower mills, vertical shaft impactor mills, and the like. Milling media include, but are not limited to, metals, silicates, and other inorganic materials in various form factors, including rods, balls, irregular shapes. In some embodiments, milling is performed on dry P-CDP powder material in a dry process to produce a finer dry powder, or on a wet aqueous slurry of P-CDP powder, with or without emulsifiers, to produce a finer particulate dispersion. Emulsifiers including, but not limited to, small molecule and polymeric surfactant compounds with nonionic, anionic, or cationic properties can be used and are readily apparent to those skilled in the art. Those skilled in the art will recognize that the fine particulate form factor provides a variety of advantages, including: (1) more stable aqueous dispersions that are less prone to separation and therefore remain uniform over time; (2) allowing for higher weight loadings, up to 50% by weight of the material in the dispersion; (3) producing particulate matter that can be uniformly coated or applied to a variety of substrates, surfaces, fibers, yarns, fabrics, and the like, producing a finished material with minimal perceptible change to the "hand"; and (4) producing dispersions that are stable to dilution and mixing with other emulsions or solutions, such as binders, surfactants, wetting agents, or softeners. In some embodiments, the final particle diameter includes less than 1 micron, 1-5 microns, 5-10 microns, 10-15 microns, and 15-20 microns, or ranges therebetween.

[0074] If larger particle sizes are desired, the composition can be granulated to form larger particle size aggregates. Thus, in some embodiments, granules (e.g., self-supporting granules) are produced from P-CDP particle powders of various sizes. Generally, this process converts P-CDP particle powders in the size form of 1-30 microns into granules of 100 microns, 200 microns, 300 microns, and larger. This process can be carried out by granulation techniques common to the pharmaceutical industry (Handbook of Granulation Technology, Ed. Parikh, DM, 2005, Taylor & Francis Group), where the powders are bonded together by physical and / or chemical means in batch or continuous mode. In the simplest form, the particles of P-CDP are mechanically blended with a fluid (e.g., aqueous) mixture containing an adhesive binder (usually a synthetic, semi-synthetic, or natural polymer). Suitable semi-synthetic polymers that can be used include cellulose ethers, specifically ethyl cellulose, methyl cellulose, hydroxypropyl cellulose, carboxymethyl cellulose, starch, and starch derivatives. Suitable fully synthetic polymers such as polyvinylpyrrolidone or polyethylene glycol can be used. Other suitable binders include sizes and other coatings used in the textile and paper industries, including polyamidoamine epichlorohydrin (PAE) or polymeric glyoxal crosslinkers, polyvinyl alcohol, and starch-based sizes. To produce durable granules that are less soluble in water or other solvents, further covalent crosslinking can be facilitated by the addition of small molecule crosslinkers such as glyoxal, formaldehyde, diisocyanate, and / or diepoxide functional groups. In addition to covalent crosslinking, electrostatic aggregation of polyelectrolytes can also be utilized as a binding motif, forming suitable adhesive properties when cationic polyelectrolytes are blended with anionic polyelectrolytes in the presence of P-CDP powder and / or supporting structures. Polycations commonly used for flocculation include, but are not limited to, polydiallyldimethylammonium chloride (polyDADMAC), acidic polyethyleneimine, and polyacrylamide. Polyanions can include those commonly used in flocculation, including, but not limited to, sodium polyacrylate, sodium polystyrene sulfonate, and polyvinyl sulfonate.

[0075] Mechanical mixing during granulation can be performed by low shear processes such as rotary drum mixing or overhead mechanical stirring. As will be readily apparent to those skilled in the art, the stirring speed and overall length of time will affect the granule particle size. Granulation can also be performed in a fluidized bed or by spray drying techniques. In either case, the P-CDP particles are combined with an aqueous or solvent-based mixture containing a binder compound, and mechanical or physical stirring is performed at a specified shear force for a set number of cycles. The resulting particles show a stepwise growth change in the average diameter of the particles and may also show a change in polydispersity. The physical properties of these granules depend on the binder selected, the crosslinking chemistry, and the physical process used for granulation. These larger granular particles are suitable for packed bed column filtration, which is commonly used in water filtration and industrial separations.

[0076] In some embodiments, the present disclosure provides a stable aqueous dispersion comprising P-CDP particles. In some embodiments, the P-CDP particles of the present disclosure that can be used in such a stable aqueous dispersion are about 1 μm to about 150 μm. For example, the P-CDP particles can be about 1, 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, 13, 14, 15, 16, 17, 18, 19, 20, 21, 22, 23, 24, 25, 26, 27, 28, 29, 30, 31, 32, 33, 34, 35, 36, 37, 38, 39, 40, 41, 42, 43, 44, 45, 46, 47, 48, 49, 50, 51, 52, 53, 54, 55, 56, 57, 58, 59, 60, 61, 62, 63, 64, 65, 66, 67, 68, 69, 70, 71, 72, 73, 74, 75, 76, 77, 78, 79, 80, 81, 82, 83, 84 , 85, 86, 87, 88, 89, 90, 91, 92, 93, 94, 95, 96, 97, 98, 99, 100, 101, 102, 103, 104, 105, 106, 107, 108, 109, 110, 111, 112, 113, 114, 115, 116, 117, 118, 119, 12 0, 121, 122, 123, 124, 125, 126, 127, 128, 129, 130, 131, 132, 133, 134, 135, 136, 137, 138, 139, 140, 141, 142, 143, 144, 145, 146, 147, 148, 149, ~ about 150 μm. The stable aqueous dispersion can be used in "grafting" applications. For example, the stable aqueous dispersion can be used in applications using chemical binders or fibrillated fibers for mechanical filling and bonding, as well as incorporation into the compacted form of thermally bonded particulates and solution-processed polymer form factors.

[0077] The P-CDP materials of the present disclosure can also be prepared on a support material (alternatively referred to as a "substrate") and can be covalently, adhesively, or mechanically bonded to a support such as a fibrous substrate. The support material can be any material having one or more groups (e.g., hydroxyl or amino, thiol, or phosphine, or other groups described herein) that can form an interaction (e.g., a covalent bond or mechanical bond) with a crosslinker or cyclodextrin. For example, one end of the crosslinker (e.g., a linking group of formula (I), (II), and / or (III)) is covalently bonded to the substrate material, and the other end of the crosslinker is covalently bonded to a reactive center on a cyclodextrin glucose unit or modified cyclodextrin (such as an acid halide or activated ester bound to the cyclodextrin). It is desirable that the support material does not dissolve (e.g., to an extent observable by visual inspection, gravimetry, or spectroscopy) under the conditions of use, e.g., in an aqueous medium. Examples of support materials include microcrystalline cellulose, cellulose nanocrystals, polymeric materials (e.g., acrylate materials, methacrylate materials, styrene materials (e.g., polystyrene), polyester materials, nylon materials, and combinations thereof), or inorganic materials (e.g., silicates, silicones, metal oxides such as alumina, titania, zirconia, and hafnia, etc. In various examples, the polymeric material is a homopolymer, copolymer, or resin (e.g., a resin containing a polymeric material). The support material can be hydroxyl- or amino-containing polymer beads or irregular particles. The support material can be in the form of a fiber (e.g., pulp, short cut, staple fiber, and continuous filament), a fiber bundle (e.g., yarn (both spun and continuous filament)), a fiber mat (e.g., nonwoven (both staple and continuous filament)), a fabric (e.g., knit, woven, nonwoven), a membrane (e.g., film, spiral wound, and hollow fiber), a cloth, a particulate (e.g., powder), or a solid surface. In some embodiments, the fibrous substrate is a cellulosic substrate. The cellulosic substrate can include any suitable form of cellulose, such as cellulose derived from a plant source, such as wood pulp (e.g., paper or paper fiber), cotton, regenerated cellulose, modified cellulosics such as cellulose esters and / or ethers, starch, polyvinyl alcohol, and derivatives thereof. The cellulosic substrate can be in the form of a fabric, such as a woven or nonwoven fabric, or as a fiber, film, or any other suitable shape that provides a particularly high surface area or porosity. In certain embodiments, the P-CDP material of the present disclosure is bonded to a fiber, e.g., a cellulosic fiber, or a fabric, such as cotton.

[0078] In addition to the substrates described in the previous paragraph, the substrate may include any of the following: polyvinylamine, polyethyleneimine, proteins, protein-based fibers (e.g., wool), chitosan and amine-containing cellulose derivatives, polyamides, vinyl chloride, vinyl acetate, polyurethane, melamine, polyimides, polystyrene, polyacrylic, polyamide, acrylate butadiene styrene (ABS), Valnox, PVC, nylon, EVA, PET, cellulose nitrate, cellulose acetate, mixed cellulose esters, polysulfone, polyethersulfone, polyvinylidene fluoride (PVDF) or polytetrafluoroethylene (PFTE or Teflon R.), polyethylene, polypropylene, polycarbonate, phosphine or thiol functional materials, and silicones or combinations thereof. The substrate may also be composed of silicon or silicon oxide, or glass (e.g., as microfibers). Suitable materials further include fabrics or synthetic or natural fiber-based materials. The material may have any form or shape, for example in the form of sheets, beads, granules, rods, fibers, foams or tubes, and may be rigid, flexible or elastic.

[0079] If necessary, the material surface can be activated by any method known in the art, such as known surface activation techniques, including, for example, corona treatment, oxygen plasma, argon plasma, selective plasma bromination, chemical grafting, allyl chemistry, chemical vapor deposition (CVD) of reactive groups, plasma activation, sputter coating, etching, or other known techniques. For example, in the case of glass surfaces, such activation is not usually required, since such surfaces are considered to be already activated herein. The purpose of the activation of the surface is to provide a surface suitable for the (direct) covalent attachment of surface-modifying functional groups or primer polymers. The surface can be further functionalized after its optional activation. The purpose of the functionalization of the surface is to provide functional groups suitable for the covalent attachment of precoat polymers.

[0080] Those skilled in the art are well aware of the various possibilities for attaching polymers to optionally activated surfaces. These techniques generally involve the introduction of amino, silane, thiol, hydroxyl and / or epoxy functional groups to the surface, followed by attachment of the polymer to the surface.

[0081] Functionalization may also include the introduction of spacers or linkers to the surface to attach the primer polymer to the surface at a predetermined distance. Suitable spacers include, for example, Alkylation of the surface may be achieved by reacting the surface with, for example, an aminoalkylsilane.

[0082] P-CDP can be attached to a substrate via a linking group of the present disclosure (e.g., via a hydroxyl or amino group of the linking group). A "linker moiety" refers to an atom that is interposed between the P-CDP and the substrate. The terms "linker" and "linking moiety" herein refer to any moiety that connects the substrate and the P-CDP to each other. The linking moiety can be a covalent bond or a chemical functional group that directly connects the P-CDP to the substrate. The linking moiety can include a series of covalently bonded atoms and their substituents, collectively referred to as the linking group. In some embodiments, the linking moiety is characterized by a first covalent bond or chemical functional group that connects the P-CDP to the first end of the linker group, and a second covalent bond or chemical functional group that connects the second end of the linker group to the substrate. The first and second functional groups may or may not be present independently and, together with the linker group, are collectively referred to as the linker moiety. The linker moiety is defined by the linking group, the first functional group, if present, and the second functional group, if present. In certain embodiments, the linker moiety comprises the intervening atoms between the P-CDP and the substrate, regardless of the source of these atoms and the reaction sequence used to synthesize the conjugate. In some embodiments, the linker moiety is an aryl moiety as described herein. In some embodiments, the linker has one or more of the following functional groups: polyfunctional isocyanate (e.g., diisocyanate), epoxy, carboxylic acid, ester, activated ester, cyanuric chloride, cyanuric acid, acid chloride, halogen, hydroxyl, amino, thiol, and phosphine.

[0083] In some embodiments, P-CDP is grafted or bonded onto microcrystalline cellulose (CMC). CMC is available in a variety of median particle sizes from about 10 to about 500 μm, including about 10 μm, 20 μm, 45 μm, 50 μm, 65 μm, 75 μm, 100 μm, 150 μm, 180 μm, 190 μm, 200 μm, 225 μm, 250 μm, 275 μm, 300 μm, 325 μm, 350 μm, 375 μm, 400 μm, 425 μm, 450 μm, 475 μm, and about 500 μm, and all particle sizes therebetween. In some embodiments, P-CDP is grafted or bonded onto CMC with a median particle size of about 50 μm. In one example, CMC is commercialized as Avicel™. In other embodiments, P-CDP is grafted or attached onto a polymeric substrate other than cellulose as described herein, whose surface has been treated to generate surface functional groups as disclosed herein, such as hydroxyl groups.

[0084] In some embodiments, the P-CDP-substrate composite (e.g., P-CDP crosslinked with an aryl linker of Formula (I)-CMC substrate composite) has a polymer thickness (i.e., the thickness of the porous P-CDP particles on the surface of the substrate) of about 1 nm to about 2000 nm. For example, the P-CDP-substrate composite has a polymer thickness of about 1, 2, 3, 4, 5, 6, 7, 8, 9, 10, 20, 30, 40, 50, 60, 70, 80, 90, 100, 150, 200, 250, 300, 350, 400, 450, 500, 550, 600, 650, 700, 750, 800, 850, 900, 950, 1000, 1050, 1100, 1150, 1200, 1250, 1300, 1350, 1400, 1450, 1500, 1550, 1600, 1650, 1700, 1750, 1800, 1850, 1900, 1950, to about 2000 nm. In some embodiments, the P-CDP-substrate complex has a polymer thickness of less than 1000 nm. In some embodiments, the P-CDP-substrate complex has a polymer thickness of about 800 nm. As will be readily apparent to one of skill in the art, having a smaller thickness (e.g., less than 1000 nm) allows for a faster rate of absorbing contaminants, e.g., aqueous contaminants.

[0085] In some embodiments, the P-CDP-substrate complex (e.g., a CMC group of formula (I)) The P-CDP (aryl linker-bridged P-CDP) composite has a contaminant adsorption capacity of up to 500 mg of contaminant per gram of CD. For example, the adsorption capacity can be up to about 1, 2, 3, 4, 5, 6, 7, 8, 9, 10, 15, 20, 25, 30, 35, 40, 45, 50, 55, 60, 65, 70, 75, 80, 85, 90, 95, 100, 105, 110, 115, 120, 125, 130, 135, 140, 145, 150, 155, 160, 165, 170, 175, 180, 185, 190, 200, 210, 220, 230, 240, 250, 260, 270, 280, 290, 300, 310, 320, 330, 340, 350, 360, 370, 380, 390, 410, 420, 430, 440, 450, 460, 470, 480, 490, 500, 510, 520, 530, 540, 550, 560, 570, 580, 590, 600, 610, 620, 630, 640, 650, 660, 670, 680, 700, 710, 720, 730 The adsorption capacity may be up to about 200 mg of contaminant per gram of CD. In some embodiments, the contaminant is an anionic microcontaminant (e.g., PFAS). In some embodiments, the cyclodextrin is a β-cyclodextrin. In some embodiments, the linking group is a linking group of formula (I), (II), and / or (III).

[0086] In some embodiments, the P-CDP-substrate complex (e.g., the P-CDP crosslinked with an aryl linker of Formula (I)-CMC substrate complex) has an equilibrium contaminant adsorption capacity of up to 500 mg of contaminant per gram of CD. For example, the equilibrium adsorption capacity is up to about 1, 2, 3, 4, 5, 6, 7, 8, 9, 10, 15, 20, 25, 30, 35, 40, 45, 50, 55, 60, 65, 70, 75, 80, 85, 90, 95, 100, 105, 110, 115, 120, 125, 130, 135, 140, 145, 150, 155, 160, 165, 170, 175 ... 5, 170, 175, 180, 185, 190, 195, 200, 210, 220, 230, 240, 250, 260, 270, 280, 290, 300, 310, 320, 330, 340, 350, 360, 370, 380, 390, 400, 410, 420, 430, 440, 450, 460, 470, 480, 490 to about 500 mg of contaminant per gram of CD. In some embodiments, the contaminant is an anionic micropollutant (e.g., PFAS). In some embodiments, the cyclodextrin is β-cyclodextrin. In some embodiments, the linking group is a linking group of formula (I), (II), and / or (III).

[0087] In some embodiments, the P-CDP-substrate complex (e.g., P-CDP crosslinked with an aryl linker of formula (I)-CMC substrate complex) has a relaxation time of less than 2 minutes. As will be appreciated by those skilled in the art, processes with long relaxation times reach equilibrium slowly, while processes with short relaxation times adapt to equilibrium quickly. In some embodiments, the contaminant is an anionic trace contaminant (e.g., PFAS). In some embodiments, the cyclodextrin is β-cyclodextrin. In some embodiments, the linking group is a linking group of formula (I), (II), or (III).

[0088] In some embodiments, any of the P-CDP materials disclosed herein are grafted or attached directly onto the CMC or via a linker group, as defined herein. In some embodiments, the P-CDP is uniformly distributed on the CMC surface. In some embodiments, the linker is an aryl linker of formula (I). In some embodiments, the linker is a linking group of formula (II). In some embodiments, the linker is a linking group of formula (III). In some embodiments, the median particle size is about 50 μm. In some embodiments, the median particle size is about 1 to about 250 μm.

[0089] CMCs are differentiated by particle shape, which is known to affect, among other things, flow properties. A non-limiting list of particle shapes includes spherical (rounded shape), rod-like, and needle-like. Particles can also be described as flat, flat and elongated, and can be characterized by aspect ratio. In some embodiments, CMC has a spherical particle shape. In some embodiments, CMC exists in the form of aggregates of smaller CMC particles. Such CMC aggregates can have a particle size ranging from 200 μm to about 2 mm. For example, the particle size of the CMC aggregates can be about 200 μm, about 300 μm, about 400 μm, about 500 μm, about 600 μm, about 700 μm, about 800 μm, about 900 μm, about 1 mm, about 1.2 mm, about 1.3 mm, about 1.4 mm, about 1.5 mm, about 1.6 mm, about 1.7 mm, about 1.8 mm, about 1.9 mm, or about 2 mm, including all ranges between these values.

[0090] In some embodiments, P-CDP is grafted or bonded onto CMC via a linking group of formula (I). In some embodiments, P-CDP is grafted or bonded onto CMC via a linking group of formula (Ia). In some embodiments, P-CDP is grafted or bonded onto CMC via a linking group of formula (II). In some embodiments, P-CDP is grafted or bonded onto CMC via a linking group of formula (III).

[0091] In some embodiments, the P-CDP of the present disclosure is grafted or bonded onto CMC via an aryl linker, and the aryl linker is uniformly distributed on the CMC crystal. In some embodiments, the median particle size is about 100 nm.

[0092] In addition to the use of CMC as shown herein, examples of other possible support materials include activated carbon, graphene oxide, and the materials mentioned above, such as silica and alumina.

[0093] In some embodiments, the supported P-CDP materials disclosed herein (e.g., the aryl linker crosslinked P-CDP of the Formula (I)-CMC substrate composite) are desirably in the form of particles having a narrow particle size dispersity. In some embodiments, the particle size distribution has a low relative span of about 5 or less, where the relative span is (D 90 -D 10 ) / D 50 It is defined by the ratio D 90 , D 50 , and D 10 are the diameters below which 90%, 50%, and 10% of the particles in the distribution have a smaller diameter, respectively. Suitable spans are less than or equal to 5, 4.5, 4, 3.5, 3, 2.5, 2, 1, 0.9, 0.8, 0.7, 0.6, 0.5, 0.4, 0.3, 0.2, or 0.1, including all ranges between these values.

[0094] In various other embodiments, P-CDP can be grafted or bonded onto cellulose nanocrystals (CNCs). CNCs are crystalline regions of cellulose microfibrils obtained after mechanical, chemical, and enzymatic treatments. Depending on the source and preparation method, CNCs are available in lengths ranging from about 1 to 1000 nm, widths ranging from about 3 to 50 nm, including all values ​​between these ranges. For example, the CNCs have a length of about 1, 2, 3, 4, 5, 6, 7, 8, 9, 10, 15, 20, 25, 30, 35, 40, 45, 50, 55, 60, 65, 70, 75, 80, 85, 90, 95, 100, 150, 200, 250, 300, 350, 400, 450, 500, 550, 600, 650, 700, 750, 800, 850, 900, 950 to about 1000 nm. The CNCs have a width of about 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, 13, 14, 15, 16, 17, 18, 19, 20, 21, 22, 23, 24, 25, 26, 27, 28, 29, 30, 31, 32, 33, 34, 35, 36, 37, 38, 39, 40, 41, 42, 43, 44, 45, 46, 47, 48, 49, or about 50. In some embodiments, the P-CDP-CNC substrate can be 2-3 times the size (length and width) of the unbound CNC. The CNCs are about 2-1 00 (George, J., et al., Cellulose nanocrystals: synthesis, functional properties, and applications. Nanotechnology, Science and Applications. 2015;8:45-54). For example, the aspect ratio of the CNCs is about 2, 5, 10, 15, 20, 25, 30, 35, 40, 45, 50, 55, 60, 65, 70, 75, 80, 85, 90, 95, 100, 105, 110, 115, 120, 125, 130, 135, 140, 145, 150, 155, 160, 165, 170, 175, 180, 185, 190, 195, or 100.

[0095] In some embodiments, P-CDP is grafted or bonded onto the CNC via a linking group of formula (I), (II), and / or (III) as described herein. In some embodiments, P-CDP is grafted or bonded onto the CMC via a linking group of formula (I). In some embodiments, P-CDP is grafted or bonded onto the CMC via a linking group of formula (II). In some embodiments, P-CDP is grafted or bonded onto the CMC via a linking group of formula (III).

[0096] In some embodiments, P-CDP is grafted or bonded onto the CNC via a linker, and the linker is uniformly distributed on the CNC crystal. In some embodiments, the median particle size is about 100 nm.

[0097] CNCs can also be differentiated by particle shape, which is known to affect flow properties, among others. A non-limiting list of particle shapes includes spherical (rounded shape), rod-like, and needle-like. Particles can also be described as flat, flat and elongated, and can also be characterized by aspect ratio. In some embodiments, CNCs have an aspect ratio between about 5 and about 100. For example, the aspect ratio can be about 5, 10, 15, 20, 25, 30, 35, 40, 45, 50, 55, 60, 65, 70, 75, 80, 85, 90, 95 to about 100. In some embodiments, the aspect ratio of the CNCs is about 20 to 25. In some embodiments, the CNCs are needle-like. In some embodiments, the CNCs exist in the form of aggregates of smaller CNC particles. Such CNC aggregates can have particle sizes 5 to 100 times larger than the individual particle sizes, depending on the size and number of particles that make up the aggregate.

[0098] In some embodiments, the substrate is a fabric or fiber. Thus, in some embodiments, the present disclosure provides a composition comprising P-CDP grafted or bonded (e.g., chemically or mechanically) to a fiber. In some embodiments, the P-CDP is grafted or bonded onto the fiber via a linker of formula (I), (II), and / or (III) as described herein. In some embodiments, the fiber is a nonwoven fiber. In some embodiments, the present disclosure provides a composition comprising P-CDP grafted or bonded (e.g., chemically, adhesively, or mechanically) to a fabric. In some embodiments, the P-CDP is grafted or bonded onto the fabric via a linker of formula (I), (II), or (III).

[0099] Fibers suitable for use include fibers comprising any of the polymers disclosed herein, such as gel spun ultra-high molecular weight polyethylene fibers (e.g., SPECTRA® fibers available from Honeywell Advanced Fibers of Morristown, NJ, and DYNEMA® fibers available from DSM High Performance Fibers Co. of The Netherlands), melt spun polyethylene fibers (e.g., CERTRAN® fibers available from Celanese Fibers of Charlotte, NC), melt spun nylon fibers (e.g., Wich Suitable fibers include, but are not limited to, fibers made from highly oriented fibers such as high tenacity nylon 6,6 fibers sold by Invista of Wichita, Kans.), melt spun polyester fibers (e.g., high tenacity polyethylene terephthalate fibers sold by Invista of Wichita, Kans.), and sintered polyethylene fibers (e.g., TENSYLON® fibers sold by ITS of Charlotte, NC). Suitable fibers also include those made from rigid rod polymers such as lyotropic rigid rod polymers, heterocyclic rigid rod polymers, and thermotropic liquid crystal polymers. Suitable fibers also include those made from regenerated cellulose, including reactive wet spun viscose rayon (Viscose sold by Birla, India or Lenzing, Austria), cuprammonium based rayon (Cupro® Bemberg sold by Asahi Kasei, Japan), or air gap spun from NMMO solvent (Tencel® sold by Lenzing, Austria). Suitable fibers made from lyotropic rigid rod polymers include poly(p-phenylene terephthalamide) fibers (e.g., KEVLAR® fibers sold by DuPont of Wilmington, Del. and TWARON® fibers sold by Teijin of Japan), and aramid fibers such as fibers made from a 1:1 copolyterephthalamide of 3,4'-diaminodiphenyl ether and p-phenylenediamine (e.g., TECHNORA® fibers sold by Teijin of Japan).Suitable fibers made from heterocyclic rigid rod polymers such as p-phenylene heterocycles include poly(p-phenylene-2,6-benzobisoxazole) fibers (PBO fibers) (e.g., ZYLON® fibers sold by Toyobo, Japan), poly(p-phenylene-2,6-benzobisthiazole) fibers (PBZT fibers), and poly[2,6-diimidazo[4,5-b:4',5'-e]pyridinylene-1,4-(2,5-dihydroxy)phenylene] fibers (PIPD fibers) (e.g., M5® fibers sold by DuPont, Wilmington, Del.). Suitable fibers made from thermotropic liquid crystal polymers include poly(6-hydroxy-2-naphthoic acid-co-4-hydroxybenzoic acid) fibers (e.g., VECTRAN® fibers sold by Celanese, Charlotte, NC). Suitable fibers also include rayon, polyacrylonitrile (e.g., OPF® fibers sold by Dow of Midland, Mich.), and carbon fibers such as those produced by high temperature pyrolysis of mesomorphic hydrocarbon tar (e.g., THORNEL® fibers sold by Cytec of Greenville, S.C.). In certain believed preferred embodiments, the yarns or fibers of the fibrous layer comprise fibers selected from the group consisting of gel spun ultra-high molecular weight polyethylene fibers, melt spun polyethylene fibers, melt spun nylon fibers, melt spun polyester fibers, sintered polyethylene fibers, aramid fibers, PBO fibers, PBZT fibers, PIPD fibers, poly(6-hydroxy-2-naphthoic acid-co-4-hydroxybenzoic acid) fibers, carbon fibers, and combinations thereof.

[0100] The P-CDP materials of the present disclosure can be adhered to such fibers by a suitable binder polymer as described herein, or can be chemically bound to such fibers by functionalizing the surface of the fiber as described herein (e.g., surface oxidation to generate surface hydroxyl groups) and forming a P-CDP in situ on the fiber surface, or by reacting an appropriately functionalized P-CDP directly with the functionalized fiber surface or indirectly through a linker moiety as described herein.

[0101] The fibers can be converted into nonwoven fabrics by different bonding methods (either before or after bonding of the P-CDP). Continuous fibers can be formed into a web using industry standard spunbond type techniques, and staple fibers can be formed into a web using industry standard carding, airlaid, or wetlaid techniques. Typical bonding methods include calendaring. These include calendering (pressure and heat), through-air heating, mechanical entanglement, hydrodynamic entanglement, needle punching, and chemical and / or resin bonding. Calendaring, through-air heating, and chemical bonding are the preferred bonding methods for starch polymer fibers. Pressure and through-air heating bonding methods require thermally bondable fibers.

[0102] The fibers of the present invention can also be bonded or combined with other synthetic or natural fibers to produce nonwoven products. The synthetic or natural fibers can be blended together in the molding process or used in separate layers. Suitable synthetic fibers include fibers made from polypropylene, polyethylene, polyester, polyacrylate, and copolymers and mixtures thereof. Natural fibers include cellulose fibers and their derivatives. Suitable cellulose fibers include those derived from any tree or plant, including hardwood fibers, softwood fibers, hemp, and cotton. Also included are fibers made by processing natural cellulose sources such as rayon.

[0103] The fibers of the present invention can be used to make nonwoven fabrics, among other suitable articles. A nonwoven article is defined as an article that contains more than 15% of a plurality of fibers that are continuous or noncontinuous, physically and / or chemically bonded to one another. The nonwoven fabric can be combined with additional nonwoven fabrics or films to make layered products that are used by themselves or as components in complex combinations of other materials. A preferred article is a disposable nonwoven article. The resulting products can find use in filters for air, oil, and water; textiles such as microfibers or breathable fabrics with improved moisture and odor absorption and softness to wear; electrostatically charged structured webs for collecting and removing dust and contaminants; textiles such as surgical drapes, wound dressings, bandages, skin patches; textiles for absorbing water and oil, such as those used to wipe up oil and water spills. The articles of the present invention can also include disposable nonwoven fabrics for hygiene and medical applications to absorb malodors. Hygiene applications include wipes; diapers, especially the topsheet or backsheet; and feminine pads or products, especially the topsheet.

[0104] The yarns or fibers of the fibrous layer can have any suitable weight per unit length (e.g., denier). Typically, the weight per unit length of the fibers is about 1 to about 50 denier per filament (1 to about 50 g per 9000 meters). The yarns include 10 to about 5000 multiple filaments.

[0105] In some embodiments, the P-CDP is adhesively bonded to a substrate such as a fiber or fabric via a binder. In some embodiments, the P-CDP is coated onto a substrate such as a fiber or fabric via a binder. In some embodiments, the P-CDP is bonded or coated to a substrate such as a fiber or fabric via a binder by introducing the surface into a stable aqueous dispersion of P-CDP particles with a binder. The P-CDP particle dispersion may be 1-50% by weight and the polymeric binder material may be present in an emulsion or solution at 1-50% by weight. For example, the P-CDP particle dispersion may be present at about 1, 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, 13, 14, 15, 16, 17, 18, 19, 20, 21, 22, 23, 24, 25, 26, 27, 28, 29, 30, 31, 32, 33, 34, 35, 36, 37, 38, 39, 40, 41, 42, 43, 44, 45, 46, 47, 48, 49, or about 50% by weight. The polymeric binder material may be present in the emulsion or solution at about 1, 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, 13, 14, 15, 16, 17, 18, 19, 20, 21, 22, 23, 24, 25, 26, 27, 28, 29, 30, 31, 32, 33, 34, 35, 36, 37, 38, 39, 40, 41, 42, 43, 44, 45, 46, 47, 48, 49, or about 50% by weight. Additional adjuvants may be used as minor components by weight to provide for wetting by the substrate (wetting agents), foaming or defoaming of the solution, softening of the substrate for hand use, and / or binding agents. The catalyst for curing can be controlled.

[0106] Various coating techniques known in the art can be applied, such as dipping and squeezing, solution casting, foam coating, or spraying the formulated solution onto the target substrate. Substrates include, but are not limited to, woven, knitted or nonwoven fabrics, continuous filament yarns, spun yarns, spun fibers, wood surfaces, and thermoplastic surfaces. In some embodiments, when the formulated solution is applied to a substrate, the combined system is dried to remove the water solvent, at which point there is a uniform film of P-CDP particles mixed with the polymer binder. In the drying process, the binder material present as an emulsion polymer flows together and becomes a continuous phase. Depending on the binder selection, the P-CDP particles are held in place by mechanical means or adhesion with the binder continuous phase only, or there may be additional covalent bonds if a hardenable binder is selected. Such covalent bonds can extend the underlying substrate, further enhancing the durability of the P-CDP particle coating.

[0107] As will be readily apparent to those skilled in the art, the resulting P-CDP particle film conforms to the shape of the underlying substrate, is resistant to physical abrasion and washing, and can be deployed into articles. Furthermore, when the P-CDP particles have access to the aqueous or gas phase within the coating, they exhibit the same selective and high affinity small molecule adsorption properties as monolithic particles. Such form factors can be translated into filter cartridges, pleated filters, nonwoven needle punch filters, hygienic nonwovens, and clothing.

[0108] A variety of binders known to those skilled in the art can be used in the context of the present disclosure, such as any of those disclosed in U.S. Patent Application Publication No. 2014 / 0178457A1, the entire contents of which are incorporated herein by reference. Suitable binders include, but are not limited to, latex binders, isocyanate binders (e.g., blocked isocyanate binders), acrylic binders (e.g., non-ionic acrylic binders), polyurethane binders (e.g., aliphatic polyurethane binders and polyether-based polyurethane binders), epoxy binders, urea / formaldehyde resins, melamine / formaldehyde resins, polyvinyl alcohol (PvOH) resins (disclosed in U.S. Patent No. 5,496,649, the entire contents of which are incorporated herein by reference) and crosslinked versions thereof, polyethylene vinyl alcohol (EvOH) and crosslinked versions thereof, polyethylene vinyl acetate (EVA), starch and starch derivatives, cellulose ether derivatives, and cellulose ester derivatives. Small molecule, polymeric or inorganic crosslinking agents may additionally be used, including formaldehyde, glyoxal, diisocyanates, diepoxides, and / or sodium tetraborate, as well as combinations thereof.

[0109] In some embodiments, P-CDP particles are mechanically bonded to a surface such as fibrillated fibers. Fibrillated fibers are used to form an extended network with high surface area that can coat and entrap particulate matter. Fibers such as fibrillated polyolefin (such as Mitsui Fybrel®), fibrillated regenerated cellulose (such as Lenzing Tencel™), and fibrillated acrylic (such as Sterling Fibers CFF™) are deployed in a wet-laid process to produce specialty papers (such as Onxy Specialty Papers, Helsa Corporation) with excellent mechanical properties, good wet strength, and the ability to retain particulate matter (U.S. Pat. No. 4,565,727, which is incorporated herein by reference in its entirety). In particular, powdered activated carbon particles with a diameter of more than 5 microns have been loaded into specialized carbon papers that are deployed in liquid and vapor filtration applications such as point-of-use water filters or cabin air filters.

[0110] In the papermaking process, an aqueous dispersion or slurry blend of short cut fibers (such as wood pulp, polyester, nylon, or polyolefin), fibrillated fibers (such as Fybrel®, Tencel™, or CFF™), and particulate powder materials are mixed (e.g., under high shear). This mixture can then be rapidly passed through a nonwoven mesh or screen to deposit a wet laid nonwoven web. The web is dried (e.g., in a hot air oven or on a heated roll) to remove the water carrier. Further bonding can be performed using a cold or hot calendar on either a flat format or patterned roll to produce a bonded specialty paper. The particulate powder used can be a dispersion of P-CDP particulates of a defined particle size. The particle size of the particulates can be set using the grinding and milling techniques defined previously. The particulate loading of the finished nonwoven can be as high as 60% by weight. The particulates can be used alone or blended with other particulates such as powdered activated carbon. Additional chemical binders such as those described herein can be used to modify or enhance the properties of the paper and are applied as would be understood by one skilled in the art.

[0111] The resulting powder-loaded paper is suitable for high loadings of P-CDP sorbent particles in a convenient paper filter form factor for water and / or air filtration. The paper can be used flat, cut into various shapes, or pleated and glued into filter media cartridges.

[0112] In some embodiments, the P-CDP particles are mechanically entangled in the yarn (e.g., continuous filament yarn). In some embodiments, the P-CDP particles are mechanically entangled in the continuous filament yarn. As will be readily apparent to those skilled in the art, a specialized subset of yarn finishes can optionally provide mechanical binding of particulate matter in the continuous filament yarn. When the yarn (e.g., continuous filament) is composed of multiple filaments of common synthetic polymers such as polyethylene terephthalate (PET) or polyamide (nylon 6 or nylon 6,6), which tend to microfibrillate on the surface of each filament, particulates can be incorporated into the yarn bundle. The P-CDP particles of the present disclosure can be incorporated into the yarn in a variety of ways. One non-limiting example is to apply a dispersion of the P-CDP particles of interest to a moving yarn bundle in a false twisting process by dip coating or oil roll application. In this process, each filament is mechanically separated by twisting first in one direction and then in the opposite direction. After the first twist, each filament is individualized, resulting in voids in the yarn bundle. A dispersion is applied at this point in the process, after which the bundle is untwisted in the normal orientation and the yarn is heated to dry the solution. This process allows for the application of dispersed particles into the yarn bundle, where the dispersed particles are held in place by the continuous filaments and the microfibrils arising from the continuous filament surface. Such an approach has been used to apply a variety of micron-sized particles, including microcapsules (US 2005 / 0262646 A1, incorporated herein by reference in its entirety), metallic silver particulates (US 2015 / 0361595 A1, incorporated herein by reference in its entirety), to continuous filament yarns, and other functional particles (US 2006 / 0067965 A1, incorporated herein by reference in its entirety) to synthetic fiber yarn bundles. These engineered, particle-filled yarns can then be processed by conventional means to form knitted and woven fabrics for use in apparel, upholstery, medical, display, or other applications.

[0113] In some embodiments, the P-CDP particles are incorporated into a thermally bonded particulate compacted form. A common form factor for powder absorbent materials is a thermally bonded compacted form. Such form factors can contain up to 95% by weight of P-CDP particles, fibrillated fibers (Fybrel®, Tencel™, or CFF™), optionally inorganic materials such as attapulgite clay, and finally organic binders. The addition of agent materials, most commonly cellulose esters and similar derivatives, forms porous composite structures with suitable mechanical strength and particulate retention efficiency for medium pressure filtration applications such as faucet filters and refrigerator filters (U.S. Pat. Nos. 5,488,021 and 8,167,141, both of which are incorporated herein by reference in their entireties).

[0114] P-CDP dry particles or dispersions can be used in place of or blended with other sorbent materials to form composite sorbent P-CDP microparticle-containing forms as described above. In such embodiments, each solid dry component can be dry blended, optionally including dry P-CDP particles with or without inorganic clay and / or fibrillated fibers, and organic binder powder. If an aqueous dispersion of P-CDP particles is used, it can be diluted with water and added to the mixture. Water is added (e.g., 80-150 wt%) and the mixture is blended (e.g., under high shear) to form a plastic material. This material can be molded into the desired form factor and dried and cured at temperatures ranging from 125-250°C. This final form factor provides P-CDP sorbent particles in a useful form factor common to point-of-use water filters.

[0115] In some embodiments, the P-CDP particles are incorporated into a solution-processed polymer form factor. Various means are available for producing filtration membrane materials. For example, solution cast films are used or hollow fibers of the membrane polymer are extruded and a condensed film of controlled pore size is formed by controlled coagulation. In some embodiments, a polymer such as cellulose acetate dissolved in a water-miscible organic solvent such as NMP, DMSO, or THF is used. The solution can be cast into a film in a water bath, which causes rapid coagulation of the cellulose acetate polymer and densification of the film. These films can be processed in a roll-to-roll machine, wrapping multiple layers to form a spiral wound membrane filter for use in microfiltration, ultrafiltration, gas filtration, or reverse osmosis applications. Common polymers used in place of cellulose acetate include polyamides, polyolefins, polysulfones, polyethersulfones, polyvinylidene fluorides, and similar modified thermoplastics. It is also possible to extrude hollow fibers into aqueous solutions to form membrane fibers by a phase inversion process known as hollow fiber membranes, which are commonly used in dialysis, reverse osmosis, and desalination applications.

[0116] In some embodiments, P-CDP particulate matter is incorporated into membrane materials to enhance their performance. For example, a small amount of P-CDP particle dispersion can be present in an aqueous coagulation bath, and this particle dispersion is incorporated into the dense or porous parts of the membrane during the phase inversion process. A second method for incorporating P-CDP particles into membranes is to incorporate a small amount of well-dispersed particles into an organic solution of the membrane polymer, and the particles are encapsulated in the membrane after coagulation. Each of these methods allows the production of polymer foams loaded with P-CDP. In various embodiments, such as microfiltration, ultrafiltration, and reverse osmosis, the incorporation of P-CDP particles acts to enhance the removal of trace contaminants in membrane systems.

[0117] In some embodiments, the P-CDP particles are incorporated into melt extruded thermoplastics (e.g., fibers and molded parts). The availability of small-diameter dry powder P-CDP particle material with low polydispersity allows the material to be incorporated into melt-processed polymer foams such as fibers and molded parts. Common thermoplastics that are useful include polyethylene terephthalate, copolyesters, polyolefins, and polyamides. Typical extrusion temperatures are 250-300°C, so the stability of the P-CDP particles to these temperatures in air (most preferred) or under inert atmosphere is required. Single- or twin-screw extrusion is used to extrude the powder material under shear at high temperatures up to 5 weight percent of the thermoplastic. The blended components, after being properly mixed, can be extruded through small round or other shaped orifices and drawn to produce fibers with a linear density of particulate matter ranging from 1 to 20 denier per filament. A common particle added to many thermoplastic fibers is titanium dioxide, which is added to whiten and mattify the fibers. P-CDP particles are added in the same manner. In the most ideal embodiment, the P-CDP particles migrate to the surface of the fiber due to their higher surface energy and exude, so that some of the particles present are accessible by the gas or liquid phase. In other embodiments, instead of extruding the polymer melt through a small orifice, it can be blown or otherwise melt processed to produce a plastic part. This plastic part also retains P-CDP particles that exude to the surface and activate to remove small molecule trace contaminants (e.g., anionic MP) from the gas and liquid phases.

[0118] The P-CDPs of the present disclosure can be supported or formed into a variety of shapes (or form factors) suitable for a variety of applications. For example, the P-CDP materials of the present disclosure can be in the form of a powder, granules, formed into a disk, e.g., from a cellulosic material such as paper or other non-woven forms, or extruded or pressed into a variety of shapes suitable, e.g., for filtration, water treatment, sample absorption, etc., as described herein.

[0119] While it is not unknown to provide adsorbents in supported form, it is important that the method used to immobilize the adsorbent to a substrate or support is robust enough to withstand the conditions of use. Additionally, the means of attachment to the substrate must not interfere with or inhibit the adsorption mechanism of the adsorbent. The adsorbents disclosed herein can be attached to a support as described herein, so that the resulting performance characteristics are minimally affected by the attachment method. In various embodiments, the supported polymeric materials of the present invention provide at least 50% of the same performance characteristics that would be provided by an adsorbent of the same composition (based on an equal amount of adsorbent) prepared without a support material when measured under the same conditions. Thus, for example, a porous material grafted to microcrystalline cellulose (e.g., P-CDP crosslinked with an aryl linker in formula (I)-CMC substrate composite) may have at least 50% of one or more of the specific performance characteristics found in an unsupported porous material tested under the same conditions.

[0120] In some embodiments, the performance characteristic can be the uptake of a particular contaminant (adsorption capacity), measured as milligrams of contaminant adsorbed per gram of P-CDP particles under specified conditions. In other embodiments, the performance characteristic can be the equilibrium adsorption capacity (q e ) can be used.

number

[0121] In yet another embodiment, the performance characteristic is the rate at which equilibrium adsorption of a contaminant is reached (the equilibrium adsorption rate of a particular adsorbent), which can be expressed as the time required for a supported or unsupported P-CDP of the present disclosure to reach equilibrium with a particular adsorbed species (or contaminant).

[0122] In yet another embodiment, the performance characteristic is the rate at which a competing adsorbent sequesteres a contaminant. The competing sorbent can be the unsupported P-CDP described herein, or other materials such as activated carbon (powdered or granular), ion exchange resins, and specialty resins used in solid-phase microextraction (e.g., HLB).

[0123] For any of these performance characteristics disclosed above, the performance of a supported P-CDP of the present disclosure will be at least about 50%, 60%, 70%, 80%, 90%, 100%, 120%, 140%, 160%, 180%, 200%, 220%, 240%, 260%, 280%, 300%, 350%, 400%, 450%, 500% or more, including all values, ranges and subranges therebetween, compared to an unsupported P-CDP of the same composition tested under essentially the same conditions, e.g., the same contaminant, temperature, pressure, exposure time, etc.

[0124] The performance characteristics of the present disclosure can be measured by a variety of methods that will be readily apparent to one of skill in the art, for example, based on bisphenol A or PFAS, or another suitable species disclosed herein. For example, contaminants can be measured at initial concentrations ranging from 1 ppb (or 1 microgram / L or 5 nM) to 1 ppt (or 1 g / L or 5 mM) of BPA or another suitable species in any aqueous sample, including, but not limited to, drinking water, wastewater, groundwater, aqueous extracts from contaminated soils, landfill leachates, purified water, or other waters that contain salts or other organic matter. The pH can range from 0 to 14. For example, the pH can be 0, 1, 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, 13, or 14, including all ranges between these values. The performance characteristics can be generally measured as described herein (e.g., in Examples 1 and 2), with typical variations (such as temperature and pressure) anticipated.

[0125] In some embodiments, the present disclosure provides articles of manufacture comprising one or more P-CDPs or one or more P-CDP-substrate complexes of the present disclosure.

[0126] In one embodiment, the article of manufacture is a protective device. In one embodiment, the article of manufacture is a garment. For example, the article of manufacture is a garment (e.g., a garment such as a uniform at least partially coated with a porous polymeric material or composition) comprising one or more P-CDPs or one or more P-CDP-substrate composites of the present disclosure. In another example, the article is a filter medium comprising one or more P-CDPs or one or more P-CDP-substrate composites of the present disclosure. The filter medium can be used as a gas mask filter. In one embodiment, the article is a gas mask comprising the filter medium. In some embodiments, the article is an extraction device.

[0127] In another embodiment, the article is a solid microphase (SPME) extraction device comprising one or more P-CDPs or one or more P-CDP-substrate complexes of the present disclosure, where the P-CDPs or P-CDP-substrate complexes are the extraction phase of the device.

[0128] In another embodiment, the article is a device for solid phase extraction of polar and semi-polar organic molecules. The device comprises one or more P-CDPs or one or more P-CDP-substrate complexes of the present disclosure instead of HLB media (hydrophilic / lipophilic balanced). The performance of the article comprising one or more P-CDPs or one or more P-CDP-substrate complexes exceeds that of HLB media.

[0129] In another embodiment, the article is a device for liquid filtration of polar and semi-polar organic molecules. The device comprises one or more P-CDPs of the present disclosure or one or more P-CDP-substrate composites (as disclosed in U.S. Pat. No. 7,655,112, which is incorporated herein by reference in its entirety) adhered into a fibrous web. Other embodiments include devices comprising P-CDP powders fused via a thermoplastic binder polymer to form a porous monolithic filter medium. (as disclosed in U.S. Pat. No. 4,753,728, the entire contents of which are incorporated herein by reference).

[0130] The P-CDP materials of the present disclosure, in various forms and form factors disclosed herein (including supported and unsupported P-CDP materials), can be used in any application where it is desirable to separate compounds (e.g., anionic or cationic MPs) from a fluid (a gas such as air, or a liquid such as water, an aqueous beverage, or a bodily fluid). The P-CDP materials can be used to "trap" or adsorb a species of interest for further analysis or quantification (e.g., in analytical testing for environmental contaminants in air or water), to separate mixtures (e.g., in chromatographic separations), or to separate desirable or valuable species that are present in dilute form in a fluid. In some embodiments, the P-CDP materials of the present disclosure can be used to purify a fluid (e.g., by removing undesirable or harmful impurities) or to isolate a desired compound from a mixture or dilute fluid solution.

[0131] In some embodiments, the present disclosure provides a method for removing one or more compounds (e.g., anionic MPs) from a fluid sample or determining the presence or absence of one or more compounds in a fluid sample, comprising: a) contacting the sample with a porous polymeric material of the present disclosure or a supported porous polymeric material of the present disclosure for an incubation period; b) separating the porous polymeric material or the supported porous polymeric material from the sample after the incubation period; c) heating the porous polymeric material or the supported porous polymeric material separated in step b) or contacting the porous polymeric material or the supported porous polymeric material separated in step b) with a solvent, thereby releasing at least a portion of the compounds from the porous polymeric material or the supported porous polymeric material; d1) optionally isolating at least a portion of the compounds released in step c) or d2) determining the presence or absence of the compounds released in step c), wherein the presence of the one or more compounds correlates with the presence of the one or more compounds in the sample. In some embodiments, the one or more cyclodextrin moieties are β-cyclodextrin moieties. In some embodiments, the determining is performed by gas chromatography, liquid chromatography, supercritical fluid chromatography, or mass spectrometry. In some embodiments, the contacting is by flowing an aqueous phase across, over, around, or through the supported porous polymeric material. In some embodiments, the aqueous sample is contacted with the P-CDP-substrate complex under static conditions for an incubation period, after which the aqueous sample is separated from the porous polymeric material. In some embodiments, the sample is a food product and the compound is a volatile organic compound. In some embodiments, the aqueous sample is drinking water, wastewater, groundwater, an aqueous extract from a contaminated soil, or a landfill leachate. In some embodiments, the sample is a perfume or fragrance and the compound is a volatile organic compound. In some embodiments, the compound is an anionic micropollutant, a heavy metal, and / or a dye.In some embodiments, the compound is an anionic MP such as a PFAS (e.g., a polyfluorinated alkyl compound and / or a perfluoroalkyl compound). In some embodiments, the PFAS is PFOA and / or PFOS.

[0132] In one embodiment, a method for purifying an aqueous sample containing one or more organic compounds is provided, the method comprising contacting the aqueous sample with a porous polymeric material of the present disclosure or a supported porous polymeric material of the present disclosure, e.g., at least 50% to at least 99% of the one or more contaminants bind to one or more cyclodextrin (e.g., β-cyclodextrin) moieties of the porous polymeric material. For example, the aqueous sample is flowed across, around, or through the porous polymeric material. In another example, the aqueous sample is subjected to a static The aqueous sample is contacted with the porous polymeric material or the supported porous polymeric material under conditions for an incubation period, and after the incubation period, the aqueous sample is separated (for example, by filtration) from the porous polymeric material.This method can be used to purify aqueous samples such as drinking water, wastewater, groundwater, aqueous extracts from contaminated soil, landfill leachate, etc.In some embodiments, the organic compound is an anionic MP such as PFAS.

[0133] In one embodiment, a method for determining the presence or absence of a compound (e.g., anionic MP) in a sample includes: a) contacting the sample with a porous polymeric material of the present disclosure or a supported porous polymeric material of the present disclosure for an incubation period (e.g., 1 minute or less, 5 minutes or less, or 10 minutes or less); b) separating the complex from a) from the sample; c) heating the composite material from b) or contacting the complex from b) with a solvent (e.g., methanol) such that at least a portion of the compound is released by the porous material; and d) determining the presence or absence of any compound, where the presence of one or more compounds correlates with the presence of one or more compounds in the sample, or isolating the compound (e.g., by filtration). For example, the determination (e.g., analysis) is performed by gas chromatography or mass spectrometry. For example, the sample is a food or beverage (e.g., milk, wine, fruit juice (e.g., orange juice, apple juice, and grape juice)), or alcoholic beverage (e.g., beer and distilled spirits) and the compound is a volatile organic compound. The porous polymeric material or supported porous polymeric material can be the extraction phase of a solid phase microextraction (SPME) device. In some embodiments, the organic compounds are anionic MPs, such as PFASs.

[0134] In one embodiment, a method for removing a compound (e.g., an organic compound) from a sample includes: a) contacting the sample with a porous polymeric material of the present disclosure or a supported porous polymeric material of the present disclosure for an incubation period, such that at least a portion of the compound is sequestered in the polymer; b) isolating the complex from a) from the sample; c) heating the complex from b) or contacting the complex from b) with a solvent (e.g., methanol), such that at least a portion of the compound is released by the porous polymeric material; and d) optionally isolating at least a portion of the compound. In some embodiments, the compound is an anionic MP, such as a PFAS.

[0135] In these methods, a variety of compounds can be addressed (e.g., sequestered, detected, and / or separated) in the process. The compound can be an organic compound. The compound can be a desired compound, such as a flavoring (e.g., a compound that affects the palatability of a food) or a pharmaceutical compound (or pharmaceutical intermediate), a contaminant (e.g., PCBs, PBAs, etc.), and / or an impurity. In some embodiments, the compound is an anionic MP, such as a PFAS. In some embodiments, the compound is gemfibrozil, oxybenzone, diclofenac, ioxynil, ketoprofen, naproxen, sulfamethoxazole, warfarin, 2,4-dichlorophenoxyacetic acid, clofibric acid, ibuprofen, 2-methyl-4-chlorophenoxyacetic acid, mecoprop, valsartan, perfluorobutanoic acid, perfluorobutanesulfonic acid, perfluoropentanoic acid, perfluoropentanesulfonic acid, perfluorohexanoic acid, perfluorohexanesulfonic acid, The anionic MP is selected from the group consisting of perfluoroheptanoic acid, perfluoroheptanesulfonic acid, perfluorooctanoic acid, perfluorooctane sulfonic acid, perfluorononanoic acid, perfluorononanesulfonic acid, perfluorodecanoic acid, perfluorodecanesulfonic acid, perfluoroundecanoic acid, perfluorododecanoic acid, perfluorotridecanoic acid, perfluorotetradecanoic acid, 2,3,3,3-tetrafluoro-2-(heptafluoropropoxy)propanoate, and combinations thereof.

[0136] Cyclodextrins are chiral. In one embodiment, chiral compounds are sequestered, detected, and / or isolated. In one embodiment, a chiral column (e.g., a preparative or analytical scale column packed with a chiral porous polymeric material or a composition comprising a chiral porous polymeric material) is used to separate and detect or isolate a single enantiomer of a compound (or at least significantly enrich a sample for one enantiomer).

[0137] In this method, the porous polymeric material or the supported porous polymeric material can be regenerated (e.g., for reuse in the method). For example, the porous polymeric material is regenerated by heating and / or exposure to a solvent (e.g., an alcohol such as methanol or ethanol, and aqueous mixtures thereof).

[0138] The following examples are presented to illustrate the present disclosure and should not be construed as limiting the disclosure. EXAMPLES

[0139] Example 1: Synthesis of β-CD-TDI polymer Reagents: β-CD: Wacker, Cavamax W7 (used as is); Tolylene-2,4-diisocyanate (TDI): Sigma Aldrich, 95%, product number T39853; N,N-Dimethylformamide (DMF): Fisher Chemical, certified ACS grade, catalog number D119-4; Water: deionized (DI) water from a Milli-Q system.

[0140] Procedure: β-CD (60.0 g, 0.0529 mol, 1 equiv.) was dissolved in 120 mL of DMF in a 500 mL one-neck round-bottom flask with a magnetic stirrer speed of 400 rpm and the temperature set at 80 °C. An oil bath equipped with a thermocouple was used for heating. After complete dissolution of β-CD, TDI (36.8 g, 0.2115 mol, 4 equiv.) was added to the flask at 80 °C. Air bubbles were observed, likely due to the presence of water in the reaction medium. After about 1 min when air bubbles had ceased to form, the flask was capped with a rubber septum. After 3 h, the reaction was stopped by adding 30 mL of methanol and stopping the heating. The resulting viscous clear solution was precipitated into 1.2 L of methanol to obtain a white powder product. After stirring for 1 h, the crude product was filtered under vacuum using a Buchner funnel. The filtered polymer powder was placed back into the 2 L beaker and washed again with 2 x 1.5 L deionized water and 1 x 1.2 L methanol. The washing time during each cycle was 1 h. After the final filtration, the wet solid product was transferred to an evaporating dish and placed in a vacuum oven at 80 °C to obtain 72.6 g of dry polymer. It was observed that starting with 6 equivalents of TDI or more resulted in a hard gel that was difficult to work up. In contrast, TDI:CD ratios ranging from 2:1 to 5:1 give powdery material upon quenching the reaction with methanol (Table 1). These polymers are also soluble in various solvents such as DMF, but not in water. See Figure 5 for a detailed comparison of the polymers in Table 1. [Table 1]

[0141] Optimization experiment of β-CD-TDI

[0142] The β-CD-TDI polymer was further optimized by studying the solubility of β-CD (neat and dried) in regular and anhydrous DMF, the results of which are shown in Table 2. Neat β-CD has a water content ranging from 12 to 14% water. [Table 2]

[0143] As shown in Table 2, the solubility of β-CD is greatly affected based on its water content. Therefore, when dry β-CD is used, the polymerization can only be carried out at a lower initial concentration, which affects the reaction yield. In contrast, the water content of DMF is only slight, which has less impact on the solubility, and it is recommended to use regular DMF for the reaction. A comparison of β-CD-TDI polymers produced in small and large batches is shown in Table 3 below. [Table 3]

[0144] While it has long been understood that the use of dry β-CD and anhydrous solvents is important to produce polyurethane-type CD polymers, as described herein, when "aqueous" solvents (also called "normal" solvents) such as DMF and / or neat β-CD are used, the resulting polymers are structurally different from those described in the literature and are more effective at sequestrating PFAS. It was unexpectedly discovered that the use of aqueous / normal solvents results in partial isocyanate reduction, as shown in Scheme 1 for TDI below. Scheme 1: Effect of water on the isocyanate groups of TDI. [ka]

[0145] The presence of amine groups in the polymerization reaction is believed to result in the formation of urea bonds in addition to the urethane bonds resulting from crosslinking of β-CD with TDI under anhydrous conditions (e.g., completely anhydrous conditions). Furthermore, the presence of free amines in the β-CD-TDI polymer is believed to contribute to the removal of PFAS. The high amine and urea content provides a polymer that is structurally different from the prior art and more advantageous for the removal of anionic micropollutants (e.g., PFAS).

[0146] Elemental analysis data showed that the final CD:TDI ratio was 1:8-1:10 when a 1:4 feed ratio was used, suggesting the presence of excess TDI units on the cyclodextrin. 1 H NMR spectroscopy shows the presence of -CH3 protons originating from amine-functionalized phenyl units (Figure 3). The amine groups can be quantified using the -CH3 peak at approximately 1.9 ppm originating from the TDI units bearing amine groups. The ratio of the integral of the -CH3 peak to the total integral of each peak gives the percentage of TDI bearing amines. Since the absolute TDI density can be calculated from the elemental analysis data, the concentration of amine groups (mmol / g) in the polymer can be calculated by correlating the NMR and EA data. See Table 4. The β-CD-TDI polymer further tested positive with a chloranil test, further confirming the presence of amines. [Table 4]

[0147] The amine-containing β-CD-TDI polymer was tested against a panel of 12 PFASs (Figure 1) and P Further testing was performed on binary mixtures of FOA and PFOS (Figure 2). The polymer (SL-1-010A) prepared with 4 equivalents of TDI showed 70% removal of PFOA and excellent removal of PFOS (96%) in only 30 minutes in panel tests, reaching nearly 90% removal of PFOA and 100% removal of PFOS in 48 hours. Similar removal performance was observed when binary mixtures of PFOA and PFOS were tested.

[0148] Example 2: Synthesis of β-CD-isocyanate polymer and PFAS removal activity Following the general procedure outlined in Example 1, β-CD-isocyanate polymers derived from 4,4'-MDI were synthesized and tested for their ability to remove PFAS.

[0149] Each polymer in Table 5 was tested for its ability to remove PFAS. All experiments were performed using 1000ng / L and 10mg / L of each of the 12 PFASs as adsorbents. Control experiments were performed without adsorbents. These experiments were performed in triplicate. Samples were taken at 0, 0.5, 9, and 48 hours. Figure 1 shows the results at 0.5 and 48 hours, with the polymers prepared from 4,4'-MDI and 2,4-TDI being particularly effective at sequestrating PFAS. Although a faster removal rate was observed with the TDI polymer (SL-1-010A), the MDI polymer (SL-0420-3) also showed good removal performance over 48 hours. The polymers obtained from 6 equivalents of TDI and MDI did not show good removal rates for either PFOA or PFOS, which is likely due to the formation of a hard gel during synthesis that prevented access to the binding sites within the particles. [Table 5]

[0150] Example 3: Synthesis of choline chloride modified β-CD-TFN polymer and PFAS removal activity In this example, a positive charge was imparted to each CD polymer to enhance the binding affinity for anionic PFAS. Without being bound to a particular theory, it is believed that the presence of phenolic groups generated in side reactions during polymerization provides the polymer with an anionic charge, reducing the polymer's uptake of PFOA and PFOS. This effect was experimentally observed with another polymer formulation, TFN-CDP, which showed excellent removal performance for a wide range of micropollutants except for those negatively charged, including PFAS. TFN-CDP can be produced on a relatively large scale using tetrafluoroterephthalonitrile (TFN) as a crosslinker. Therefore, it was desired to modify the adsorption properties of PFAS by incorporating a positive charge into the polymer backbone. In this example, choline chloride (a quaternary ammonium salt with a hydroxyl group) was selected as an additive to the polymerization reaction of TFN-CDP. Choline chloride is incorporated into the polymer because it can react with TFN in the same way as β-CD. This polymer is hereinafter referred to as TFN-CDP+ (Scheme 2). Scheme 2: Overview of the synthesis of choline chloride modified β-CD-TFN polymer [ka] [Table 6] [Table 7] [Table 8]

[0151] Prior to measuring PFAS removal rates, a comparison was made between TFN-CDP and TFN-CDP+ for the uptake rates of BPA (a neutral molecule) and methyl orange (MO, a negatively charged dye molecule). While the uptake rate of BPA was unaffected, the uptake rate of MO was significantly improved, from approximately 30% for TFN-CDP to over 99% for TFN-CDP+. As expected, the TFN-CDP+ polymer showed significantly lower affinity for positively charged molecules such as methylene blue compared to TFN-CDP (Table 9, Figure 7). Based on this preliminary data, TFN-CDP+ was tested for removal rates of environmentally relevant concentrations of PFOA and PFOS. [Table 9]

[0152] Although further experiments are required to fully characterize the adsorption mechanism, this approach allows (1) to utilize dual binding mechanisms (inclusion complex with β-CD and ionic interactions) simultaneously in a single material and (2) to enhance the binding affinity of the inclusion complex due to the presence of positive charges near the CD cavity. Furthermore, TFN-CDP+ is synthesized in one step, and the amount of positive charges incorporated can be easily modified by changing the amount of choline chloride used in the reaction.

[0153] Experimental procedure: β-CD (1 g, 0.881 mmol), TFN (1.06 g, 5.286 mmol), K2CO3 (2.44 g, 17.621 mmol), choline chloride (0.37 g, 2.643 mmol), and 5.4 mL of H2O / DMSO (2:3, v / v) were added to a 20 mL scintillation vial equipped with a magnetic stirrer. The mixture was stirred at 60 °C for 20 h. Additional solvent (1 mL) was added after the first hour of stirring. After 20 h, 10 mL of water was added and the polymer was dispersed by stirring for 30 min. After filtration, the crude product was transferred to a centrifuge tube. The sample was washed three times with hot methanol (~40 mL) (30 min each cycle). After decanting the methanol, deionized water (~30 mL) was added. 1 M HCl was added dropwise while stirring the sample until the pH stabilized between 3-4. The crude product was washed two more times with hot methanol (approximately 40 mL). The final methanol wash was filtered under vacuum and the product was dried at 80° C. overnight.

[0154] Testing PFOA and PFOS Removal Performance - PFAS adsorption experiments were performed to measure the removal performance of the different TFN-CDP+ polymers. To facilitate the screening process of a large number of polymer formulations, adsorption kinetics studies were performed using a mixture of 12 PFASs in nanopure water. Understanding of adsorption kinetics is essential as it reveals information about the adsorbent dosage and required contact time relevant to the treatment process. This panel experiment not only gives insight into the uptake rates of PFOA and PFOS, but also allows for the evaluation of performance against other PFASs such as GenX and short- and long-chain PFASs, thereby determining the broad-spectrum PFAS removal capabilities of these polymers. The results, summarized in Figure 1, show the percent removal of each PFAS at 30 minutes and 48 hours of contact time. These experiments were performed in triplicate using approximately 1 ppb of each of the 12 PFASs in nanopure water at a polymer loading of 10 mg / L. Control experiments without adsorbent were also performed and the reported percent removals are corrected for the amount of loss observed in the control experiments. All polymers were sieved through a 230 mesh screen.

[0155] Impressively, two derivatives of TFN-CDP+ (i.e., MB-1-036 and MB-1-037, prepared from 3 and 6 equivalents of choline chloride, respectively) showed the best removal performance among all polymers tested, with nearly complete removal of all PFASs in the panel. MB-1-037 showed effective removal of GenX and short-chain PFASs in addition to PFOA and PFOS over a 30-minute period, likely due to its high quaternary ammonium loading (Figure 2).

[0156] After initial screening under panel experiments, the polymers were selected by narrowing down the removal evaluation using binary mixtures of PFOA and PFOS (Table 10). In this particular task, all adsorption experiments were performed using 0.5 ppb PFOA and 1 ppb PFOS at a polymer loading of 10 mg / L. A control experiment without adsorbent was performed and all measurements were performed in triplicate. Samples from each solution were taken for analysis at predefined time points: 0, 0.5, 2, 4, 8, and 24 hours. The polymers selected for these measurements were SL-1-010A (TDI), MB-1-036 (TFN+CC), and MB-1-037 (TFN+CC). All polymers tested showed high removal of PFOS over 24 hours, but SL-1-010A (TDI) and the two TFN-CDP+ derivatives showed high removal (>90%) only in 30 minutes. With regard to PFOA removal, although SL-1-010A(TDI) performed similarly to the panel experiments, MB-1-036 and MB-1-037 outperformed the other two polymers in terms of both kinetics and 24-h removal capacity.

[0157] [Table 10]

[0158] Trace pollutant adsorption experiment

[0159] β-CD is known to form stable inclusion complexes with trace pollutants. BPA and MO were selected as model compounds to test the uptake of neutral and negatively charged trace pollutants, respectively, to understand the adsorption mechanism in the choline chloride-modified TFN-CDP polymer. Furthermore, the thermodynamic parameters of the tested materials can be determined by fitting the trace pollutant adsorption data as a function of concentration to the Langmuir model (Eqs. 1 and 2).

[0160] The single-site Langmuir model, assuming a homogeneous adsorption surface, is given as follows:

number

number

[0161] In the case of choline chloride modified TFN-CDP polymers, the maximum MO capacity (q max,1 The adsorption kinetics of the second adsorption site (q max,2 ) showed maximum loading capacities of 37.3 and 33.0 mg / g, both of which were the maximum capacities (q max = 37.6 mg / g), which is very close to the data. L and K. L,2 The similarity between the values ​​of K suggests that the second adsorption site of the choline chloride-modified TFN-CDP polymer is related to MO adsorption within the cavities of CDs. L,1 and K. L,2 A comparison of the K values ​​also indicates a significantly stronger first adsorption site that can be attributed to the interaction of anionic MO molecules with quaternary ammonium sites. The BPA adsorption data were fitted using a single-site Langmuir model, which revealed similar K values ​​for all three polymers. L The saturation uptake values ​​were determined and showed the presence of similar adsorption sites for neutral molecules. The maximum BPA capacities of the two choline chloride modified TFN-CDP polymers were 112.1 and 100.1 mg / g, whereas the capacity of the unmodified TFN-CDP was 106.1 mg / g (Table 11, Figure 9). Notably, these saturation uptake values ​​are in good agreement with the density of CD sites for these polymers. This observation also suggests that BPA adsorption occurs within the cavities of CDs.

[0162] [Table 11]

[0163] Example 4: Synthesis of choline chloride modified β-CD-TDI polymer and its PFAS removal activity β-CD (2 g, 1.76 mmol, 1 equiv.) was dissolved in 5 mL of DMF in a 20 mL scintillation vial equipped with a magnetic stir bar at a stirring speed of 400 rpm and a temperature of 80° C. 4 g of choline chloride was dissolved in 10 mL of DMSO at 80° C. to a concentration of 0.4 g / mL. Various stoichiometric ratios of choline chloride solutions ((0.3075 mL, 0.1230 g, 0.5 equiv.), (0.6150 mL, 0.2460 g, 1 equiv.), (0.9225 mL, 0.369 g, 1.5 equiv.), or (1.2300 mL, 0.492 g, 2 equiv.)) were added to the β-CD solution at 80° C. After mixing at 80°C for 5 min, toluene diisocyanate (2,4-TDI, 1.8417 g, 10.57 mmol, 6 equiv.) was added. Bubbles, likely due to moisture in the reaction, were observed after the addition of the diisocyanate. The vial was capped approximately 1 min after the bubbles subsided. After 3 h, the reaction was stopped by adding 10 mL of methanol and turning off the heat. After the addition of methanol, a white powder product precipitated. The mixture was transferred to a 50 mL polypropylene centrifuge tube. After centrifugation, the solvent was decanted and the crude product was washed with water (2 x 40 mL) and methanol (2 x 40 mL). For each washing cycle, the mixture was stirred for 30 min followed by centrifugation. For the final cycle, the product in methanol was filtered under vacuum and dried overnight at 80°C. FIG. 10 shows the structure of choline chloride modified β-CD-TDI polymer prepared with 1:6:1 molar equivalents of β-CD:TDI:choline chloride at 80 °C in 5 mL DMF for 3 h. 1 The H NMR spectrum is shown. The presence of urethane and urea groups between 7.75 and 9.5 ppm indicates successful incorporation of choline chloride into the polymer. 1The H NMR spectrum also shows the following chemical shifts: 6.75-7.75 ppm (protons from aromatic rings of TDI); 5.5-6 ppm (protons from -OH groups attached to C2 and C3 of β-CD); 4.8-5 ppm (protons attached to C1 of β-CD); 4.25-4.75 ppm (protons from -OH group attached to C6 of β-CD); 4.1 ppm (protons from -O-CH2- group of choline chloride); 3.5-4 ppm (protons attached to C2-C6 of β-CD); 3.3-3.5 ppm (protons from water); 3.1-3.2 ppm (protons from -CH3 group of choline chloride); 2.5 ppm (DMSO); 1.9-2.1 ppm (protons from -CH3 group of TDI); the peaks marked with asterisks are due to residual solvent. Figure 11 shows a comparison of the choline chloride modified β-CD-TDI polymer with the β-CD-TDI polymer, where the main difference is the broad peak centered at 3.13 ppm. The sharp peaks at 4.1 ppm and 3.1-3.2 ppm are due to unreacted choline chloride. Figure 12 shows a comparison of three choline chloride modified β-CD-TDI polymers with different choline chloride loadings, supporting the view that as the amount of choline chloride increases, the peak intensity at 3.13 ppm increases.

[0164] Following the synthetic procedures outlined above, various polymers were prepared with different stoichiometric equivalents as shown in Table 12 below. Additionally, the PFOA incorporation of the polymers was tested. These results show that the incorporation of choline chloride into the β-CD-TDI polymer allows for the controlled addition of cationic charge to the polymer, increasing the incorporation of PFOA from 70% to 99% when compared to the SL-1-010A polymer (Table 12). See also Figure 13.

[0165] [Table 12]

[0166] Equivalent While the present invention has been described in conjunction with the specific embodiments set forth above, many alternatives, modifications and other variations will be apparent to those skilled in the art, and all such alternatives, modifications and variations are intended to fall within the spirit and scope of the present invention. References (1)Richardson,SD;Ternes,TAAnal.Chem.2018,90,398-428. (2)Carpenter,CMG;Helbling,DEEnviron.Sci.Technol.2018,52,6187-6196. (3)Barry,V.Winquist,A.Steenland,K.Environ.Health Perspect.2013,121,1313-1318. (4)Gallo, V.;Leonardi,G.;Genser,B.;Lopez-Espinosa,M.-J.;Frisbee,SJ;Karlsson,L.;Ducatman,AM;Fletcher,T.Environ.Health Perspect.2012,120,655-660. (5)Melzer,D.;Rice,N.;Depledge,MH;Henley,WE;Galloway,TSEnviron.Health Perspect.2010,118,686-692. (6) DeWitt, JCDietert, RR, Ed.;Molecular and Integrative Toxicology;Springer International Publishing: Cham,2015. (7)Diamanti-Kandarakis,E.;Bourguignon,J.-P.;Giudice,LC;Hauser,R.;Prins,GS;Soto,AM;Zoeller,RT;Gore,ACEndocr.Rev.2009,30,293-342. (8)Vajda,AM;Barber,LB;Gray,JL;Lopez,EM;Woodling,JD;Norris,DOEnviron.Sci.Technol.2008,42,3407-3414. (9)Tetreault,GR;Bennett,CJ;Shires,K.;Knight,B.;Servos,MR;McMaster,MEAquat.Toxicol.2011,104,278-290. (10)Gagne,F.;Bouchard,B.;Andre,C.;Farcy,E.;Fournier,M.Comp.Biochem.Physiol.- C Toxicol.Pharmacol.2011,153,99-106. (11)Alsbaiee,A.;Smith,BJ;Xiao,L.;Ling,Y.;Helbling,DE;Dichtel,WRNature 2016,529,190-194. (12)Alzate-Sanchez,DM;Smith,BJ;Alsbaiee,A.;Hinestroza,JP;Dichtel,WRChem.Mater.2016,28,8340-8346. (13)Ling,Y.;Klemes,MJ;Xiao,L.;Alsbaiee,A.;Dichtel,WR;Helbling,DEEnviron.Sci.Technol.2017,51,7590-7598. (14)Xiao,L.;Ling,Y.;Alsbaiee,A.;Li,C.;Helbling,DE;Dichtel,WRJAm.Chem.Soc.2017,139,7689-7692. (15)Ji,W.;Xiao,L.;Ling,Y.;Ching,C.;Matsumoto,M.;Bisbey,RP;Helbling,DE;Dichtel,WRJAm.Chem.Soc.2018,140,12677-12681. (16)Klemes,M.J.;Ling,Y.;Chiapasco,M.;Alsbaiee,A.;Helbling,D.E.;Dichtel,W.R.Chem.Sci.2018,9,8883-8889. (17)Li,C.;Klemes,M.J.;Dichtel,W.R.;Helbling,D.E.J.Chromatogr.A 2018,1541,52-56. (18) D’Agostino,L.A.;Mabury,S.A.Env iron.Sci.Technol.2017,51,13603-13613. (19)Barzen-Hanson,K.A.;Roberts,S.C.;Choyke,S.;Oetjen,K.;McAlees,A.;Riddell,N.;McCrindle,R.;Ferguson,P.L.;Higgins,C.P.;Field,J.A.Environ.Sci.Technol.2017,51,2047-2057. (20)Breysse,P.N.U.S Departement of Health and Human Services: Agency for Toxic Substances and Disease Registry: Toxicological profile for Perfluoroalkyls.2018. (21)Hu,X.C.;Andrews,D.Q.;Lindstrom,A.B.;Bruton,T.A.;Schaider,L.A.;Grandjean,P.;Lohmann,R.;Carignan,C.C.;Blum,A.;Balan,S.A.;et al.Environ.Sci.Technol.Lett.2016,3,344-350. (22)Kannan,K.;Corsolini,S.;Falandysz,J.;Fillmann,G.;Kumar,KS;Loganathan,BG;Mohd,MA;Olivero,J.;Van Wouwe,N.;Yang,JH;et al.Environ.Sci.Technol.2004,4948-495. (23)Sun,M.;Arevalo,E.;Strynar,M.;Lindstrom,A.;Richardson,M.;Kearns,B.;Pickett,A.;Smith,J.;Knappe,DRUEnviron.Sci.Technol.Lett.2016,3,415-419. (24)Eschauzier,J.;Beerendonk,E.;Scholte- Veenendaal,P.;De Voogt,P.Environ.Sci.Technol.2012,46,1708-1715. (25)Xiao,L.;Ching,C.;Ling,Y.;Nasiri,M.;Klemes,MJ;Reineke,TM;Helbling,DE;Dichtel,WR(Submitted to Chem.Mater.December 2018) 2019,1-9. (26)Mason,CR;Maynard-Atem,L.;Heard,KWJ;Satilmis,B.;Budd,PM;Friess,K.;Lanc,M.;Bernardo,P.;Clarizia,G.;Jansen,JCMacromolecules 2014,47,1021-1029. (27)Vojkovsk,T.Pept.Res.1995,8,236-237. (28)Marik,J.;Song,A.;Lam,KSTetrahedron Lett.2003,44,4319-4320. (29)Buckley,D.;Henbest,HB;Slade,PJChem.Soc.1957,4891,4891.

[0167] According to a preferred embodiment of the present invention, for example, the following is provided: (Section 1) Formula (I):

change

change

change

change

change

change

change

change

Claims

1. 2,4-toluene diisocyanate, 2,6-toluene diisocyanate, 4,4'-methylene diphenyl diisocyanate, 2,4'-methylene diphenyl diisocyanate, 1,3-bis(isocyanatomethyl)benzene, 1,3-bis(1-isocyanato-1-methylethyl)benzene, 3,3'-dichloro-4,4'-diisocyanato-1,1'-biphenyl, 3,3'-dimethyl-4,4'-biphenylene diisocyanate, 1. A porous polymeric material comprising a plurality of cyclodextrins crosslinked with a plurality of aryl diisocyanate crosslinkers comprising 4,4′-oxybis(phenylisocyanate), 1,3-phenylene diisocyanate, 1,4-phenylene diisocyanate, 4-chloro-6-methyl-1,3-phenylene diisocyanate, and / or 1-chloromethyl-2,4-diisocyanatobenzene, wherein one or more of the plurality of cyclodextrins comprises: Formula (I): 【Chemistry 42】 and binding to a linker of During the ceremony, A is, 【Chemistry 1】 is an aryl moiety represented by the formula: 【Chemistry 3】 represents any of the substituents bonded to A in formula (I), W is 【Chemical 43A】 and a is 2; Z is -N(Me) 3 + and L is, 【Chemistry 44】 and A' is a covalent bond to A; Z′ is a covalent bond to Z; *teeth, 【Chemistry 45】 is a covalent bond to 【Chemistry 46】 is the point of attachment to a cyclodextrin carbon atom of one of the cyclodextrins, x is 0, y 1 is 1, y 2 is 1, y 3 is 0, Porous polymeric materials.

2. 2. The porous polymeric material of claim 1, wherein each cyclodextrin is selected from the group consisting of α-cyclodextrin, β-cyclodextrin, γ-cyclodextrin, and combinations thereof.

3. the aryl diisocyanate crosslinking agent is 4,4'-methylenediphenyl diisocyanate, and the aryl moiety is 【Chemistry 50】 where x and y 3 13. The porous polymeric material of claim 1, wherein each of

4. 4. The porous polymeric material of claim 3, wherein each cyclodextrin is a β-cyclodextrin.

5. The linker comprising formula (I) has the following structure: 【Chemistry 52】 and the oxygen atom designated * is a glycosidic oxygen from one of said plurality of cyclodextrins.

6. 11. A method for purifying a fluid sample containing one or more contaminants, the method comprising contacting the fluid sample with the porous polymeric material described in claim 5, whereby at least 50% by weight of the total amount of the one or more contaminants in the fluid sample is adsorbed onto the porous polymeric material.

7. The aryl diisocyanate crosslinker is toluene 2,4-diisocyanate, and the aryl moiety is 【Chemistry 53】 where x and y 3 13. The porous polymeric material of claim 1, wherein each of

8. 8. The porous polymeric material of claim 7, wherein each cyclodextrin is a β-cyclodextrin.

9. The linker comprising formula (I) has the following structure: 【Chemistry 55】 and the oxygen atom designated * is a glycosidic oxygen from one of said plurality of cyclodextrins.

10. 10. A method for purifying a fluid sample containing one or more contaminants, the method comprising contacting the fluid sample with the porous polymeric material described in claim 9, whereby at least 50% by weight of the total amount of the one or more contaminants in the fluid sample is adsorbed onto the porous polymeric material.

11. The porous polymer material is 10 m 2 / g to 2000m 2 13. The porous polymeric material of claim 1 having a surface area of ​​1 / g.

12. 11. A method for purifying a fluid sample containing one or more contaminants, the method comprising contacting the fluid sample with the porous polymeric material described in claim 1, whereby at least 50% by weight of the total amount of the one or more contaminants in the fluid sample is adsorbed onto the porous polymeric material.

Citation Information

Patent Citations

  • Cyclodextrin polymer separating material

    JP2001504879A

  • Phenol compound removal method

    JP2005125193A

  • Globular cyclodextrin polymer, method for producing the same, and adsorbent containing the same

    JP2006083379A

  • Carrier for immobilizing microorganism

    JP2010119389A

  • Method for selectively adsorbing / removing halogenated aromatic compound contained in medium by using cyclodextrin polymer

    JP2013233473A